Method for preparing positive electrode active material

JP7933977B2Active Publication Date: 2026-10-13SEMICON ENERGY LAB CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2025135759
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2026-10-13
Estimated Expiration
2040-09-08

AI Technical Summary

Benefits of technology

【0034】 本発明の一態様により、欠陥(ピットまたはクラックなど)の発生を抑制することができ る。本発明の一態様により、高エネルギー密度であり、且つ、充放電容量の大きい正極活 物質を提供することができる。または、高エネルギー密度であり、且つ、充放電電圧の高 い正極活物質を提供することができる。または、劣化が少ない正極活物質を提供すること ができる。または、新規な正極活物質を提供することができる。または、充放電容量の大 きい二次電池を提供することができる。または、充放電電圧の高い二次電池を提供するこ とができる。または、安全性または信頼性の高い二次電池を提供することができる。また は、劣化が少ない二次電池を提供することができる。または、長寿命の二次電池を提供す ることができる。または、新規な二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933977000002
    Figure 0007933977000002
  • Figure 0007933977000003
    Figure 0007933977000003
  • Figure 0007933977000004
    Figure 0007933977000004
Patent Text Reader

Abstract

To provide a positive electrode active material having a large charge-discharge capacity, or to provide a positive electrode active material having a high charge-discharge voltage, or to provide a positive electrode active material exhibiting less degradation, or to provide a novel positive electrode active material.SOLUTION: To suppress the occurrence of defects, the surface of positive electrode active material particles is modified or coated by adding zirconium (Zr), titanium (Ti), hafnium (Hf), yttrium (Y), to the positive electrode active material particles. Ideally, a barrier film containing at least one of Zr, Ti, Hf, and Y is provided around the positive electrode active material particles, and it is preferable that the barrier film be a functional film capable of allowing lithium ions to pass through while suppressing the elution of metals such as cobalt from the inside of the positive electrode active material particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This relates to a secondary battery using a positive electrode active material and a method for manufacturing the same. Or, a portable device having a secondary battery. Regarding information terminals, vehicles, etc.

[0002] One aspect of the present invention relates to a product, a method, or a method of manufacture. Alternatively, the present invention relates to a process. This relates to machines, manufacturers, or compositions of matter. One aspect of the present invention relates to semiconductor devices, display devices, light-emitting devices, energy storage devices, lighting devices, electronic devices, Or relating to methods for manufacturing them.

[0003] In this specification, "electronic equipment" refers to all devices that have an energy storage device, and the energy storage device is All electronic devices, including electro-optical devices and information terminal devices with energy storage systems, are considered electronic equipment.

[0004] In this specification, the term "energy storage device" refers to all elements and devices that have an energy storage function. For example, energy storage devices such as lithium-ion secondary batteries (also called secondary batteries), Lithium This includes um ion capacitors and electric double-layer capacitors. [Background technology]

[0005] In recent years, lithium-ion secondary batteries, lithium-ion capacitors, air batteries, all-solid-state batteries, etc. The development of various energy storage devices is thriving, particularly high-power, high-capacity lithium-ion batteries. The demand for rechargeable batteries has expanded rapidly alongside the development of the semiconductor industry, and they represent a source of rechargeable energy. As a source of supply, it has become indispensable in today's information society.

[0006] Furthermore, a positive electrode active material for lithium-ion secondary batteries that offers high capacity and excellent charge-discharge cycle characteristics. As a production method, research has been conducted on a technique of synthesizing lithium cobalt oxide, then adding lithium fluoride and a manganese fluoride, followed by mixing and heating (Patent Document 1). Research has been conducted on a technique of adding magnesium fluoride, mixing the resultant, and heating the mixture (Patent Document 1).

[0007] In addition, research on the crystal structure of positive electrode active materials has also been conducted (Non-Patent Document 1 to Non-Patent Document 3). Further, properties of fluorides such as fluorite (calcium fluoride) have been studied for a long time (Non-Patent Document 4). Additionally, by using the ICSD (Inorganic Crystal Structure Database) introduced in Non-Patent Document 5, research on X-ray diffraction (XRD) analysis of the crystal structure of positive electrode active materials has been carried out. [Prior Art Documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Unexamined Patent Publication No. 2019-179758 [Non-Patent Documents]

[0009] [Non-Patent Document 1] Toyoki Okumura et al, "Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation", Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et al, “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16) ,2009, 165114 [Non-Patent Document 3] Zhaohui Chen et al, “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12) A1604-A1609 [Non-Patent Document 4] WE Counts et al, Journal of the American Ceramic Society, 1953, 36[1] 12-17. Fig.01471 [Non-Patent Document 5] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., 2002, B58 364-369. [Overview of the Initiative] [Problems that the invention aims to solve]

[0010] The characteristics required of energy storage devices include safety in various operating environments and improved long-term reliability. These are some examples.

[0011] Rechargeable batteries used in electric vehicles and hybrid vehicles are designed for long-term use. Therefore, sufficient reliability is desired. Used in electric vehicles and hybrid vehicles. The rechargeable batteries used must have high voltage and heat resistance.

[0012] Furthermore, in order to shorten the charging time of the secondary battery, the ability to perform rapid charging is also desirable. ru.

[0013] One aspect of the present invention aims to provide a positive electrode active material with a large charge / discharge capacity.

[0014] Alternatively, one of the objectives is to provide a positive electrode active material with a high charge / discharge voltage. Alternatively, degradation The challenge is to provide a small amount of positive electrode active material, or to provide a novel positive electrode active material. The challenge is to address the following issues.

[0015] Alternatively, one of the objectives is to provide a secondary battery with a large charge / discharge capacity. One of the challenges is to provide a high-voltage secondary battery. Alternatively, to provide a high level of safety or reliability. One of the objectives is to provide a secondary battery that is less prone to degradation. One of the challenges is to provide a long-life secondary battery. Furthermore, one of the objectives is to provide a novel secondary battery.

[0016] Alternatively, one aspect of the present invention provides a secondary system that can be used over a wide temperature range and is less affected by ambient temperature. One of the challenges is providing batteries.

[0017] Furthermore, one aspect of the present invention provides a novel substance, active material, energy storage device, or method for producing the same. This will be one of the challenges.

[0018] Furthermore, the description of these problems does not preclude the existence of other problems. The embodiments do not need to solve all of these problems. It is possible to extract other issues from the description of the requested terms. [Means for solving the problem]

[0019] By charging and discharging under high voltage conditions of 4.5V or higher or at high temperatures (45°C or higher), the process progresses. Defects in the positive electrode active material particles (also called pits) can occur due to charging and discharging. Defects such as cracks occur due to the expansion and contraction of positive electrode active material particles. In some cases, this may be the case.

[0020] To suppress the occurrence of such defects, zirconium (Zr) and titanium are used in the positive electrode active material particles. By adding (Ti), hafnium (Hf), yttrium (Y), etc., positive electrode active material particles are created. Surface modification or surface coating is performed on the child. Ideally, a barrier film (Z) is applied around the positive electrode active material particles. A barrier film containing one of r, Ti, Hf, or Y is provided, and the barrier film allows lithium ions to pass through. This allows for the creation of a functional film that suppresses the leaching of metals such as cobalt from within the positive electrode active material particles. This is preferable. Furthermore, it is not limited to forming a coating film over the entire surface of the particles, but rather to allow metal elements to leach out. A configuration may also be adopted in which a barrier film is provided on a part of the area to block the vulnerable region.

[0021] Such barrier films are preferably made robust in order to withstand high charge and discharge voltages. By gradually increasing the heating temperature, or slowly raising the heating temperature, the crystalline A high film thickness is preferable.

[0022] Furthermore, after adding fluorine or a metallic element (magnesium) to the positive electrode active material particles, A barrier layer may be formed on the surface of the positive electrode active material particles by heat treatment. It can be said that the A layer forms the outer shell of the positive electrode active material particles, with the shell being the barrier layer and the core being the positive electrode. If considered as active material particles, it can also be called a core-shell structure. The barrier layer, like the barrier film, is lithium It can pass through mu ions and suppresses the leaching of metals such as cobalt from inside the positive electrode active material particles. It is preferable that it has a function. In this specification, when it is formed on the outermost surface of the positive electrode active material particles. This is called a barrier film, and when it is formed below the outermost surface of the positive electrode active material particles, i.e., in the depth direction, it is called a barrier. Let's call it a layer.

[0023] The barrier film or barrier layer suppresses the occurrence of various defects (such as pits or cracks). This improves the safety or reliability of secondary batteries.

[0024] The positive electrode active material of lithium-ion secondary batteries is typically LCO or NCM, and consists of multiple metals. It can also be described as an alloy containing elements (such as cobalt and nickel). At least one component has a defect, and that defect may change before and after charging and discharging. Positive electrode activity When material particles are used in a secondary battery, the environmental substances (electrolyte) surrounding the positive electrode active material particles become The phenomenon of chemical or electrochemical corrosion or deterioration of the material due to (etc.) This can occur. This degradation does not occur uniformly on the particle surface, but rather concentrates locally. This can occur, and repeated charging and discharging of secondary batteries can cause defects to develop, for example, from the surface to the interior. To do.

[0025] The phenomenon in which defects progress and form holes in positive electrode active material particles is called pitting corrosion. This can also be called a porrosion, and the hole created by this phenomenon is referred to as a pit in this specification. Call.

[0026] In this specification, cracks and pits are distinct. Cracks appear immediately after the production of cathode active material particles. Even if present, no pits exist. Pits are under high voltage conditions of 4.5 V or higher or at high temperatures (45 °C or higher) during charging and discharging, and can be described as holes from which several layers of cobalt and oxygen have been extracted, and can also be described as locations where cobalt has been eluted. Cracks refer to new surfaces formed by the application of physical pressure, or cracks caused by grain boundaries. Cracks may also occur due to expansion and contraction of particles during charging and discharging. In addition, pits may also form from cracks or cavities inside particles. It can also be regarded as a site where ruthenium is eluted. Cracks refer to new surfaces generated by the application of physical pressure, or cracks caused by grain boundaries. Cracks may also occur due to expansion and contraction of particles during charging and discharging. In addition, pits may also be generated from cracks or voids within particles. surface, or a crack caused by a grain boundary. Cracks may also occur due to expansion and contraction of particles during charging and discharging. In addition, pits may also be generated from cracks or voids inside particles. Expansion and contraction may cause cracks. In addition, pits may also be generated from cracks or voids in particles. Pits may also occur.

[0027] Figure 35(C) shows an example of a pit. Figure 35(A) is a cycle test at a charging voltage of 4.7 V After 50 cycles, the secondary battery cell was disassembled, and a FIB-SEM image of the positive electrode active material particles was obtained. is a top view, the cross-sectional view of the broken line portion in Figure 35(A) is Figure 35(B), and Figure 3 The enlarged view of the portion enclosed by the square frame in 5(B) is Figure 35(C). Pits 90a, 90b, and 90c indicated by arrows in Figure 35(C) are shown. The pits 90a, 90b, and 90c indicated by arrows are shown.

[0028] By adding Zr, Ti, Hf, Y, etc. to the positive electrode active material particles, the occurrence of pits during charging and discharging under high voltage conditions or high temperatures can be suppressed. The generation of pits during charging and discharging can be suppressed.

[0029] <Observation Using SEM> Three-dimensional structural information can be obtained by repeating cross-section processing with FIB and SEM observation. Note that such an observation method is sometimes called Slice and View. There is.

[0030] The configuration of the invention relating to the method for manufacturing a secondary battery disclosed in the present specification includes a first step of preparing a first mixture in which a first material, a second material, and a third material are mixed, and a first step of preparing a first mixture in which the first material, the second material, and the third material are mixed, and a first step of preparing the first mixture The second step involves heating to produce a second mixture, and mixing the second mixture with the fourth material. A third step to prepare a third mixture, and the third mixture, a fifth material and a sixth A fourth step is to prepare a fourth mixture in which the materials are mixed, and the fourth mixture is heated to a first temperature A fifth step involves heating under certain conditions to produce a fifth mixture, and then crushing the fifth mixture. The crushed fifth mixture is heated at a temperature higher than the first temperature condition, and the sixth mixture is heated. The process includes a sixth step of manufacturing, and comprises the second step, the fifth step, and the sixth step In the first step, heating is carried out in an oxygen-containing atmosphere, and in the second step, heating is 6 The process is carried out within a temperature range of 00°C to 950°C and for a period of 1 hour to 100 hours. The temperature conditions in 1 are a temperature range of 350°C or higher and less than 600°C, and a duration of 1 hour or more and less than 100 hours. The experiment was conducted within the specified range, with the second temperature condition being a temperature range of 600°C to 900°C for 1 hour. The above describes a method for producing a positive electrode active material, which is carried out within a timeframe of 100 hours or less.

[0031] In the above configuration, the first material is a halogen compound having an alkali metal, and the second is The material contains magnesium, and the third material is a metal containing alkali metals and cobalt. The oxides are such that the fourth material has nickel, and the fifth material has aluminum.

[0032] Furthermore, in the above configuration, the sixth material is zirconium (Zr), titanium (Ti), and HAF. It is preferable to have one or more of nium (Hf) and yttrium (Y), In particular, the presence of zirconium is even more desirable.

[0033] The above manufacturing method involves heating under the first temperature conditions to create crystals on the surface of the positive electrode active material particles. Crystal growth is performed, and by heating under the second temperature condition, the surface and vicinity of the positive electrode active material particles, This is a method for manufacturing a secondary battery, which involves providing a barrier film containing crystals on all or part of the surface layer. That's also true. [Effects of the Invention]

[0034] According to one aspect of the present invention, the occurrence of defects (such as pits or cracks) can be suppressed. According to one aspect of the present invention, a positive electrode activity with high energy density and large charge / discharge capacity is provided. A material can be provided, or a material with high energy density and high charge / discharge voltage. It is possible to provide a positive electrode active material. Or, it is possible to provide a positive electrode active material that does not degrade easily. This can be done. Or, a novel positive electrode active material can be provided. Or, a large charge / discharge capacity can be achieved. We can provide a high-performance secondary battery. Or, we can provide a secondary battery with a high charge / discharge voltage. This can be done. Or, it can provide safe or reliable secondary batteries. This can provide a secondary battery with less degradation, or a secondary battery with a long lifespan. It is possible to do so. Or, a novel secondary battery can be provided.

[0035] Furthermore, according to one aspect of the present invention, novel materials, active materials, energy storage devices, or methods for producing them are proposed. It can be provided.

[0036] Furthermore, the description of these effects does not preclude the existence of other effects. The embodiment does not necessarily have to have all of these effects. Furthermore, other effects are... This will become clear from the description in the specification, drawings, claims, etc., and the specification, drawings Furthermore, it is possible to extract other effects from the descriptions in the claims and other documents. [Brief explanation of the drawing]

[0037] [Figure 1] Figure 1 is a diagram illustrating the method for preparing the positive electrode active material. [Figure 2] Figure 2 illustrates the method for preparing the positive electrode active material. [Figure 3] Figure 3 illustrates the method for preparing the positive electrode active material. [Figure 4] Figure 4 shows an example of a scanning electron microscope (SEM) image of a cathode active material. [Figure 5] Figure 5 shows an example of a SEM image of a cathode active material. [Figure 6] Figure 6 shows an example of a SEM image of a cathode active material. [Figure 7] Figure 7 shows an example of a scanning electron microscope (SEM) image of a cathode active material. [Figure 8] Figure 8 illustrates the charging depth and crystal structure of a positive electrode active material according to one embodiment of the present invention. [Figure 9] Figure 9 shows the XRD pattern calculated from the crystal structure. [Figure 10] Figure 10 illustrates the charging depth and crystal structure of the positive electrode active material in the comparative example. [Figure 11] Figure 11 shows the XRD pattern calculated from the crystal structure. [Figure 12] Figures 12(A) to (D) are cross-sectional views illustrating examples of the positive electrode of a secondary battery. [Figure 13] Figure 13(A) is an exploded perspective view of a coin-type rechargeable battery, Figure 13(B) is a perspective view of a coin-type rechargeable battery, and Figure 13(C) is a cross-sectional perspective view thereof. [Figure 14] Figure 14(A) shows an example of a cylindrical secondary battery. Figure 14(B) shows an example of a cylindrical secondary battery. Figure 14(C) shows an example of multiple cylindrical secondary batteries. Figure 14(D) shows an example of an energy storage system with multiple cylindrical secondary batteries. [Figure 15] Figures 15(A) and 15(B) illustrate examples of secondary batteries, while Figure 15(C) shows the inside of a secondary battery. [Figure 16]Figures 16(A) to 16(C) illustrate examples of secondary batteries. [Figure 17] Figures 17(A), 17(B), and 17(C) show the external appearance of a secondary battery. [Figure 18] Figures 18(A) to 18(C) illustrate the method for manufacturing a secondary battery. [Figure 19] Figure 19 is a top view showing an example of a secondary battery manufacturing apparatus. [Figure 20] Figure 20 is a cross-sectional view showing an example of a method for manufacturing a secondary battery. [Figure 21] Figures 21(A) to 21(C) are perspective views showing an example of a method for manufacturing a secondary battery. Figure 21(D) is a cross-sectional view corresponding to Figure 21(C). [Figure 22] Figures 22(A) to 22(F) are perspective views showing an example of a method for manufacturing a secondary battery. [Figure 23] Figure 23(A) shows an example of the battery pack configuration, Figure 23(B) shows an example of the battery pack configuration, and Figure 23(C) shows an example of the battery pack configuration. [Figure 24] Figures 24(A) and (B) illustrate examples of secondary batteries. [Figure 25] Figures 25(A) through (C) illustrate examples of secondary batteries. [Figure 26] Figures 26(A) and (B) illustrate examples of secondary batteries. [Figure 27] Figure 27(A) is a perspective view of a battery pack showing one embodiment of the present invention, Figure 27(B) is a block diagram of the battery pack, and Figure 27(C) is a block diagram of a vehicle having a motor. [Figure 28] Figures 28(A) to (D) illustrate an example of a transport vehicle. [Figure 29] Figures 29(A) and 29(B) illustrate an energy storage device according to one embodiment of the present invention. [Figure 30] Figure 30(A) shows an electric bicycle, Figure 30(B) shows a secondary battery for an electric bicycle, and Figure 30(C) illustrates an electric motorcycle. [Figure 31] Figures 31(A) to 31(D) illustrate an example of an electronic device. [Figure 32] Figure 32(A) shows an example of a wearable device, Figure 32(B) shows a perspective view of a wristwatch-type device, and Figure 32(C) is a diagram illustrating the side view of a wristwatch-type device. [Figure 33] Figure 33 shows the cycle characteristics of a secondary battery. [Figure 34] Figures 34(A) and (B) are SEM images of the positive electrode. [Figure 35] Figures 35(A) to (C) are SEM images of the positive electrode. [Figure 36] Figures 36(A) to (C) are SEM images of the positive electrode. [Figure 37] Figures 37(A) to (C) are SEM images of the positive electrode. [Figure 38] Figures 38(A) to (C) are SEM images of the positive electrode. [Figure 39] Figures 39(A) to (C) are STEM images of the positive electrode. [Figure 40] Figures 40(A) and (B) are STEM images of the positive electrode. [Figure 41] Figures 41(A) to (C) show the EDX analysis results of the positive electrode. [Modes for carrying out the invention]

[0038] The embodiments of the present invention will be described in detail below with reference to the drawings. However, the present invention is... Not limited to the following description, the form and details can be modified in various ways, as any person skilled in the art would know. This is easily understood. Furthermore, the present invention shall be interpreted as being limited to the contents of the embodiments described below. It's not something that can be done.

[0039] A secondary battery has, for example, a positive electrode and a negative electrode. The positive electrode is made up of a positive electrode active material. The positive electrode active material is, for example, a substance that performs a reaction that contributes to the charge and discharge capacity. The substance may include, in part, substances that do not contribute to the charge and discharge capacity.

[0040] In this specification, the positive electrode active material of one aspect of the present invention is a positive electrode material, or a positive electrode active material for a secondary battery. It may be expressed as an electrode material, a composite oxide, etc. Also, in this specification, etc., one aspect of the present invention The positive electrode active material preferably contains a compound. Furthermore, in this specification, etc., the present invention In one embodiment, the positive electrode active material preferably has a composition. Furthermore, in this specification, etc., this In one embodiment, the positive electrode active material preferably has a composite structure.

[0041] In this specification, segregation refers to the segregation of a solid composed of multiple elements (e.g., A, B, C). This refers to the phenomenon in which a certain element (for example, B) is distributed non-uniformly in space.

[0042] In this specification, the surface layer of particles such as active material refers, for example, to a distance of 50 degrees from the surface toward the interior. Within nm, more preferably within 35 nm, even more preferably within 20 nm, most preferably This refers to a region within 10 nm. Surfaces created by cracks and fissures can also be considered surfaces. The region deeper than the surface is called the interior. Furthermore, in this specification, a grain boundary refers to, for example, a particle Areas where particles are stuck together, areas where the crystal orientation changes within the particle (including the central part), and areas with many defects. This refers to areas containing grains, areas where the crystal structure is disordered, etc. Grain boundaries can be considered a type of surface defect. The vicinity of a grain boundary refers to the region within 10 nm of the grain boundary. Furthermore, in this specification, etc. The term "particle" is not limited to referring only to spherical particles (with a circular cross-section), but also to the cross-sectional shape of individual particles. Examples include elliptic, rectangular, trapezoidal, conical, rounded quadrilateral, and asymmetrical shapes. Furthermore, individual particles may have an amorphous shape.

[0043] Furthermore, Miller indices are used to indicate crystal planes and directions in this specification. Individual planes are represented by ( ). Crystal planes, directions, and space groups are notated by superscripts in crystallography. A bar is used, but in this specification, due to the restrictions on application notation, instead of putting a bar above the number, the number It is sometimes expressed with a minus sign (-) before it.

[0044] (Embodiment 1) In this embodiment, Figures 1, 2, and 3 are used to describe a method for producing a positive electrode active material according to one aspect of the present invention. Let me explain an example of the law.

[0045] <Step S11> As step S11 in Figure 1, first, a composite oxide having lithium, transition metal M, and oxygen. A lithium source and a transition metal M source are prepared as materials for (LiMO2).

[0046] Lithium sources include, for example, lithium carbonate, lithium hydroxide, lithium nitrate, and lithium fluoride. Um, etc., can be used.

[0047] As a transition metal M, layered rock salt-type composite oxides belonging to the space group R-3m along with lithium are used. It is preferable to use a metal that can form the compound. For example, a small amount of manganese, cobalt, and nickel. Even if not, one can be used. In other words, cobalt alone can be used as the transition metal M source. Alternatively, nickel alone may be used, or two types, cobalt and manganese, or cobalt and nickel. You may use two types of nickel, or you may use three types: cobalt, manganese, and nickel.

[0048] When using a metal capable of forming layered rock salt-type composite oxides, it can adopt a layered rock salt-type crystal structure. It is preferable to use a mixture ratio of cobalt, manganese, and nickel within a certain range. Also, layered rock salt Aluminum may be added to these transition metals to the extent that they can adopt a specific crystal structure.

[0049] As the transition metal M source, oxides, hydroxides, etc. of the above-mentioned metals are used as examples of transition metal M. This can be done. As a cobalt source, for example, cobalt oxide, cobalt hydroxide, etc. can be used. This can be done. Manganese sources such as manganese oxide and manganese hydroxide can be used. It can be done. Nickel oxide, nickel hydroxide, etc. can be used as nickel sources. Aluminum oxide, aluminum hydroxide, etc. can be used as a source of luminium. ru.

[0050] <Step S12> Next, in step S12, the lithium source and the transition metal M source are mixed. The mixing is done dry. This can be done by a chemical or wet process. For mixing, for example, a ball mill or bead mill can be used. This can be done. When using a ball mill, for example, zirconia balls can be used as the grinding medium. It is preferable to use it.

[0051] <Step S13> Next, in step S13, the mixed materials are heated. This step is followed by a subsequent heating step. To distinguish between the two, the terms "baking" or "first heating" are sometimes used. Heating is performed at temperatures of 800°C or higher, up to 1100°C. It is preferable to perform the procedure at temperatures below ℃, and more preferably at temperatures between 900℃ and 1000℃. A temperature of around 950°C is more preferable. Or a temperature of 800°C to 1000°C is preferable. Or A temperature of 900°C to 1100°C is preferred. If the temperature is too low, the lithium source and transition metal There is a risk that the decomposition and melting of the M source will be insufficient. On the other hand, if the temperature is too high, the transition metal M When used as such, the metal responsible for the oxidation-reduction reaction is excessively reduced, lithium evaporates, etc. Defects may occur due to the cause. For example, if cobalt is used as the transition metal M, A defect in which the luto becomes divalent may occur.

[0052] The heating time can be, for example, between 1 hour and 100 hours, or between 2 hours and 20 hours. It is preferable to do so. Or, it is preferable to do so for 1 hour or more and 20 hours or less. Or, 2 hours or more and 1 A firing time of 0 hours or less is preferable. The firing should be carried out in a low-moisture atmosphere such as dry air (e.g., dew point -50°C). The following is more preferably carried out at -100°C or below. For example, 1000°C The heating will be carried out over a period of time, with a temperature increase of 200°C / h and a flow rate of 10 L / min of the dry atmosphere. This is preferable. The heated material can then be cooled to room temperature (25°C). For example It is preferable that the cooling time from the specified temperature to room temperature be between 10 hours and 50 hours.

[0053] However, cooling to room temperature in step S13 is not mandatory. If there are no problems in performing steps 1 through S44, the cooling will be performed to a temperature higher than room temperature. You may do so.

[0054] <Step S14> Next, in step S14, the material that was calcined above is recovered, and lithium, transition metal M and A complex oxide (LiMO2) containing oxygen is obtained. Specifically, lithium cobalt oxide, man Lithium gunnate, lithium nickelate, and cobalt in which some of the cobalt is replaced with manganese. Lithium oxide, lithium cobalt oxide in which some of the cobalt is replaced with nickel, or nickel Lithium ru-manganese-cobaltate, etc., is obtained.

[0055] Furthermore, step S14 includes pre-synthesized lithium, transition metal M, and oxygen. A composite oxide may be used. In this case, steps S11 to S13 can be omitted. It is possible.

[0056] For example, as a pre-synthesized composite oxide, cobalt acid manufactured by Nippon Chemical Industrial Co., Ltd. Lithium particles (product name: Cellseed C-10N) can be used. These are average particles. The diameter (D50) is approximately 12 μm, and the impurity content was determined by glow discharge mass spectrometry (GD-MS). In the analysis, the magnesium concentration and fluorine concentration were 50 ppm wt or less, and the calcium concentration was 50 ppm wt or less. The aluminum and silicon concentrations are 100 ppm wt or less, and the nickel concentration is 1 Sulfur concentration less than 50 ppm wt, sulfur concentration less than 500 ppm wt, arsenic concentration 1100 ppm Below wt, the concentration of other elements other than lithium, cobalt, and oxygen is 150 ppm w It is lithium cobalt oxide, with a value of t or less.

[0057] Alternatively, lithium cobalt oxide particles manufactured by Nippon Chemical Industrial Co., Ltd. (product name: Cellseed C-5) H) can also be used. This has an average particle size (D50) of approximately 6.5 μm, and GD- In impurity analysis by MS, the concentrations of elements other than lithium, cobalt, and oxygen were C-1 This is lithium cobalt oxide, which is equivalent to or less than 0N.

[0058] In this embodiment, cobalt is used as the metal M, and pre-synthesized lithium cobalt oxide is used. We will use um particles (Cellseed C-10N manufactured by Nippon Chemical Industrial Co., Ltd.).

[0059] <Step S21> Next, in step S21, a halogen source such as a fluorine source or a chlorine source is added as a material for mixture 902. Prepare a lithium source and a magnesium source. It is also preferable to prepare a lithium source.

[0060] Examples of fluorine sources include lithium fluoride (LiF) and magnesium fluoride (MgF2). Aluminum fluoride (AlF3), titanium fluoride (TiF4, TiF3), fluoride cobalt Fluorine (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (Zr F4), vanadium fluoride (VF5), manganese fluoride (MnF2, MnF3), fluoride Iron (FeF2, FeF3), chromium fluoride (CrF2, CrF3), niobium fluoride (Nb F5), zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride ( NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (C) eF2), lanthanum fluoride (LaF3), sodium aluminum hexafluoride (Na3Al F6) and others can be used. Alternatively, a mixture of multiple fluorine sources may be used. Lithium fluoride has a relatively low melting point of 848°C and melts easily in the annealing process described later. Therefore, it is preferable.

[0061] For example, lithium chloride, magnesium chloride, etc., can be used as a chlorine source.

[0062] Magnesium sources include, for example, magnesium fluoride, magnesium oxide, and magnesium hydroxide. Cium, magnesium carbonate, etc., can be used.

[0063] For example, lithium fluoride and lithium carbonate can be used as lithium sources. Furthermore, lithium fluoride can be used as both a lithium source and a fluorine source. Magnesium oxide can be used as both a fluorine source and a magnesium source.

[0064] In this embodiment, lithium fluoride (LiF) is prepared as the fluorine source, and the fluorine source and magnesium Magnesium fluoride (MgF2) will be used as the source of nexium. Lithium fluoride (L) iF and magnesium fluoride (MgF2) are in a molar ratio of approximately LiF:MgF2 = 65:35. When mixed, it has the greatest effect in lowering the melting point. On the other hand, when the amount of lithium fluoride increases, lith There are concerns that an excess of lithium fluoride could worsen the cycle characteristics. Therefore, lithium fluoride The molar ratio of iF to magnesium fluoride (MgF2) is given by LiF:MgF2=x:1 (0≦x≦1 9) is preferable, and LiF:MgF2=x:1 (0.1≦x≦0.5) is more Preferably, LiF:MgF2=x:1 (near x=0.33) is even more preferable. In detailed specifications, "neighborhood" refers to a value greater than 0.9 times the value and less than 1.1 times the value.

[0065] Furthermore, if the following mixing and grinding steps are performed wet, a solvent must be prepared. The solvent is acetone. Ketones such as ethanol, alcohols such as ethanol and isopropanol, and diethyl ether Examples of ethers, dioxanes, acetonitriles, N-methyl-2-pyrrolidone (NMP), etc. You can use an aprotic solvent that does not react easily with lithium. This is more preferable. In this embodiment, acetone will be used.

[0066] <Step S22> Next, in step S22, the materials of the above mixture 902 are crushed and mixed. This can be done dry or wet, but wet grinding is preferred because it allows for finer grinding. It seems. For mixing, for example, a ball mill, bead mill, etc. can be used. When used, it is preferable to use zirconia balls as the grinding medium, for example. It is preferable to thoroughly perform the mixing and grinding steps to finely pulverize the mixture 902.

[0067] <Step S23> Next, in step S23, the materials mixed and ground above are recovered, and the mixture 90 Get 2.

[0068] Mixture 902, for example, has a median diameter (D50) of 600 nm or more and 20 μm or less. Preferably, the thickness is 1 μm or more and 10 μm or less. Or 600 nm or less. The particle size is preferably 10 μm or less, or 1 μm to 20 μm. If the mixture 902 is modified, a composite having lithium, transition metal M and oxygen can be made in a later step. When mixed with an oxide, it facilitates the uniform distribution of mixture 902 on the surface of the composite oxide particles. stomach.

[0069] <Step S41> Next, in step S41, the LiMO2 obtained in step S14 and the mixture 902 Mix ,. Number of atoms of transition metal in a composite oxide containing lithium, transition metal and oxygen. The ratio of M to the number of magnesium atoms (Mg) in mixture 902 is M:Mg = 100:y It is preferable that (0.1 ≤ y ≤ 6), and M:Mg = 100:y (0.3 ≤ y ≤ 3). It is preferable to have a certain state.

[0070] The mixing in step S41 is performed in a manner that does not destroy the composite oxide particles, similar to the mixing in step S12. It is preferable to use milder conditions. For example, the rotation speed may be higher than that of the mixing in step S12. It is preferable to use conditions with a small amount of particles or a short processing time. Also, dry processing is preferable to wet processing in terms of particle size. It can be said that these are conditions that make it difficult to destroy. For mixing, for example, a ball mill or bead mill can be used. This is possible. When using a ball mill, for example, zirconia balls can be used as the grinding medium. It is preferable to use [this].

[0071] <Step S42> Next, in step S42, the materials mixed above are collected to obtain mixture 903.

[0072] In this embodiment, a mixture of lithium fluoride and magnesium fluoride is used to remove impurities. Although a method of adding to a small amount of lithium cobalt oxide is described, one aspect of the present invention is This is not limited to this. Instead of mixture 903 in step S42, lithium cobalt oxide starting material You may also use a material that has been calcined with a magnesium source and a fluorine source added to it. This includes the processes of steps S11 to S14 and steps S21 to S23. Because there is no need to separate the processes, it is simple and highly productive.

[0073] Alternatively, using lithium cobalt oxide to which magnesium and fluorine have been pre-added. This is also fine. If lithium cobalt oxide with added magnesium and fluorine is used, step Steps up to S42 can be omitted, making the process simpler.

[0074] Furthermore, lithium cobalt oxide, which already contains magnesium and fluorine, is further treated with magnesium. A magnesium source and a fluorine source may be added.

[0075] <Step S43> Next, in step S43, the mixture 903 is heated in an oxygen-containing atmosphere. This is sometimes called the first annealing to distinguish it from other heating processes. This heating is performed on mixture 9 To prevent the 03 particles from sticking together, it is preferable to use heating that has an anti-adhesion effect.

[0076] Heating methods that have an anti-adhesion effect include, for example, heating the mixture 903 while stirring, and the mixture Heating while vibrating the container containing 903 is one possible method.

[0077] The heating temperature in step S43 is above the temperature at which the reaction between LiMO2 and mixture 902 proceeds. It is necessary to do so. The temperature at which the reaction proceeds here refers to the elemental temperature of LiMO2 and mixture 902. Any temperature at which interdiffusion occurs is sufficient. Therefore, it does not need to be lower than the melting temperature of these materials. For example, in salts and oxides, the melting temperature T m 0.757 times (Tammann temperature T) d )mosquito Solid-phase diffusion occurs.

[0078] However, the reaction proceeds more easily if the temperature is above the melting point of at least a portion of mixture 903. This is preferable. Therefore, it is preferable that the annealing temperature be above the eutectic point of mixture 902. If compound 902 contains LiF and MgF2, the temperature in step S43 is set to the eutectic point of 7 A temperature of 42°C or higher is preferable.

[0079] Also, the molar ratio of LiCoO2:LiF:MgF2 is 100:0.33:1. The mixed mixture 903 showed endothermic reaction at around 830°C in differential scanning calorimetry (DSC measurement). A peak is observed. Therefore, an annealing temperature of 830°C or higher is more preferable. Material 903 has at least fluorine, lithium, cobalt, and magnesium. Mixture 903 has an O3' type crystal structure.

[0080] A higher annealing temperature allows the reaction to proceed more easily, shortens the annealing time, and increases productivity. Therefore, it is preferable.

[0081] However, the annealing temperature must be above the decomposition temperature of LiMO2 (1130°C in the case of LiCoO2). It needs to be below the temperature. Also, at temperatures near the decomposition temperature, LiMO2 decomposes, albeit in trace amounts. This is a concern. Therefore, the annealing temperature is preferably 1130°C or lower. It is more preferably 1000℃ or lower, even more preferably 950℃ or lower, and 900 It is even more preferable if the temperature is below ℃.

[0082] Therefore, the annealing temperature is preferably between 500°C and 1130°C, and above 500°C. A temperature of 1000°C or less is more preferable, a temperature of 500°C or more and 950°C or less is even more preferable, and 500°C A temperature of 900°C or higher is even more preferable. Furthermore, a temperature of 742°C or higher and 1130°C or lower is preferable. A temperature of 42°C to 1000°C is more preferable, and a temperature of 742°C to 950°C is even more preferable. A temperature of 742°C to 900°C is more preferable. Also, a temperature of 830°C to 1130°C is preferable. More preferably, temperatures between 830°C and 1000°C are preferable, and even more preferably between 830°C and 950°C are preferable. Preferably, the temperature is between 830°C and 900°C.

[0083] Furthermore, when heating mixture 903, the partial pressure of fluorine or fluoride in the atmosphere is set to an appropriate range. It is preferable to control it to that extent.

[0084] In the manufacturing method described in this embodiment, some materials, such as LiF which is a fluorine source, are used as a flux. This function allows the annealing temperature to be below the decomposition temperature of LiMO2, for example, 7 It can be cooled to temperatures between 42°C and 950°C, and magnesium is dispersed in the surface layer compared to the core. By distributing the target additives at a high concentration, it is possible to produce a positive electrode active material with excellent properties.

[0085] However, since LiF is lighter than oxygen molecules, it can volatilize and dissipate when heated. As a result, the amount of LiF in mixture 903 decreases, and its function as a flux weakens. Therefore, L It is necessary to heat the fluorine while suppressing the volatilization of iF. Even if that were the case, there is a possibility that Li and F on the LiMO2 surface would react to form LiF, which would then volatilize. Yes. Therefore, even if a fluoride with a higher melting point than LiF is used, the same suppression of volatilization will be achieved. Control is necessary.

[0086] Therefore, heating the mixture 903 in an atmosphere containing LiF, that is, Li in the heating furnace It is preferable to heat the mixture 903 when the partial pressure of F is high. This can suppress the volatilization of LiF in compound 903.

[0087] Annealing is preferably carried out for an appropriate amount of time. The appropriate annealing time depends on the annealing temperature. The size and composition of the LiMO2 particles in step S14 vary depending on the conditions. For smaller sizes, lower temperatures or shorter durations may be preferable than for larger sizes.

[0088] For example, if the average particle size (D50) of the particles in step S14 is about 12 μm, the annealing temperature The temperature is preferably between 600°C and 950°C. The annealing time is preferably 3 hours or more. More preferably 10 hours or more, and even more preferably 60 hours or more.

[0089] On the other hand, if the average particle size (D50) of the particles in step S24 is about 5 μm, the annealing temperature For example, a temperature of 600°C to 950°C is preferred. The annealing time is, for example, 1 hour to 10 hours. Less than two hours is preferable, and about two hours is more preferable.

[0090] The cooling time after annealing is preferably, for example, 10 hours or more and 50 hours or less.

[0091] <Step S31> Next, in step S31, an additive source is prepared. Examples of elements contained in the additive source include, for example, Zirconium, aluminum, nickel, manganese, titanium, vanadium, iron, chromium One or more elements selected from niobium, cobalt, arsenic, zinc, silicon, sulfur, phosphorus, and boron are used. It is possible. Figure 1 shows an example using nickel and aluminum sources as additive sources. I will explain about this.

[0092] The additive sources are preferably oxides, hydroxides, fluorides, alkoxides, etc.

[0093] <Step S61> Next, in step S61, the annealed mixture 903 is mixed with the additive source. It can also be said that the additive is incorporated into the surface of the mixture 903 after the process.

[0094] Mixing methods include, for example, solid-phase methods, sol-gel methods, sputtering methods, and mechanochemical methods. CVD methods can be used. Solid-phase and sol-gel methods are simple and can be performed at atmospheric pressure and room temperature. It is preferable that the surface of the annealed mixture 903 may contain additives.

[0095] In this specification, the sol-gel method refers to a method in which a solution of an organic compound of a metal is used as a starting material. The hydrolysis and polymerization of the compounds inside the solution results in the formation of fine particles of metal oxides or hydroxides. The mixture is initially dissolved in a sol, and the reaction is further advanced to form a porous gel, which is an amorphous material. This refers to a method of creating a film or crystal by heating.

[0096] When using the sol-gel method, first, the alkoxide of the additive source is dissolved in alcohol, and Mix the mixture 903 after Neil with the other ingredients.

[0097] For example, when using zirconium as an additive source, zirconium(IV) tetrapropion Hoxides can be used. As for alcohols, for example, isopropanol (2 -Propanol can be used.

[0098] Next, zirconium(IV) tetrapropoxide in isopropanol solution and after annealing. Stir the mixture with mixture 903. Stirring can be done, for example, with a magnetic stirrer. This can be done. The stirring time is when the water in the atmosphere and zirconium(IV) tetrapropoxide are added. Any time sufficient for the decomposition and polycondensation reactions to occur, for example, 60 hours at room temperature. This can be done under the following circumstances.

[0099] After the above processing is complete, the precipitate is recovered from the mixture. Recovery methods include filtration and centrifugation. Evaporation to dryness can be applied. In this embodiment, recovery is performed by evaporation to dryness. In this embodiment, the drying process is carried out by ventilation at 95°C.

[0100] <Step S62> Next, in step S62, the dried material is recovered to obtain mixture 904.

[0101] <Step S63> Next, the mixture 904 synthesized in step S62 is heated. (S43 is the first annealing step) In this case, the heating in S63 can be called a second annealing. The heating conditions are 350°C or higher. The process should be carried out within a temperature range of less than 600°C and for a period of 1 to 100 hours.

[0102] Furthermore, heating in an oxygen-containing atmosphere is preferable.

[0103] In this embodiment, heating is performed at 400°C for 2 hours.

[0104] <Step S64> Step S64 involves crushing and mixing if necessary.

[0105] <Step S67> Next, the mixture recovered in step S64 is heated. (S63 is called the second annealing.) In total, the heating in S63 can also be called the third annealing. The heating time is when holding at the specified temperature. It is preferable to perform the procedure with an interval of 50 hours or less, and more preferably with an interval of 2 hours or more and 10 hours or less. Furthermore, it is even preferable to carry out the activity for between one and three hours.

[0106] The specified temperature is preferably between 600°C and 1200°C, and between 800°C and 1000°C. This is preferable.

[0107] Furthermore, heating in an oxygen-containing atmosphere is preferable.

[0108] In this embodiment, the specified temperature is set to 850°C and maintained for 2 hours, with the heating rate increasing by 200°C. The flow rate of the dry atmosphere is set to 10 L / min / h.

[0109] In this embodiment, steps S63 and S67 are performed twice under different heating conditions. Although the heat treatment is performed separately, it is not particularly limited, and in step S63, the heating conditions are set to be a single process. The temperature range should be between 830°C and 1130°C, and the heating time should preferably be, for example, 1 hour or more. More preferably 10 hours or more, and even more preferably 60 hours or more. If this is done, it will not be necessary to perform the heat treatment in two separate stages, and in that case, the number of steps can be reduced. .

[0110] <Step S68> Step S68 involves crushing and mixing if necessary.

[0111] <Step S66> Next, in step S66, the material crushed above is recovered and the positive electrode active material 100 is prepared. This can be done. At this time, it is preferable to further sift the recovered particles. By applying this method, if the positive electrode active material particles are stuck together, this can be resolved. Cut.

[0112] Figure 4 shows an example of an SEM image of the positive electrode active material 100 obtained according to the flow chart in Figure 1. The manufacturing process for the positive electrode active material 100 shown in Figure 4 differs between step S63 and step S67. Instead of dividing the heating into two stages under the same heating conditions, in step S63, the heating conditions are set to 830°C or higher for 11 The temperature range was set to 30°C or lower, and the heating time was 850°C for 10 hours in an oxygen atmosphere. Nickel and aluminum were used as additive sources. The surface of the positive electrode active material 100 shown in Figure 4 is smooth. It has a smooth surface with few bumps or irregularities. Being smooth and having few irregularities is, for example, a cross-sectional SEM image of the positive electrode active material 100 as shown in Figure 4. This can be determined from the cross-sectional TEM image, the specific surface area of ​​the positive electrode active material 100, etc. Positive electrode active material Since the shape of 100 particles is rarely perfectly spherical and is irregular, it is difficult to determine the radius of curvature. This is difficult, as the radius of curvature changes if the particle size changes, making it difficult to define. Although this is difficult, the cross-sectional shape obtained by cutting the positive electrode active material 100 at an arbitrary position, The edges are almost entirely free of sharp corners, and the edges can be made into a rounded shape. Fluorine is important for making the surface smooth or shiny. Fluorine improves the wettability of the positive electrode active material surface, homogenizing it and creating a smooth surface. The mixture is being flattened. For example, in step S43, lithium oxide and fluoride are mixed. It is important to produce positive electrode active material particles by heating them. Positive electrode active material in Figure 4 In 100, a region containing fluorine is formed on the surface as a barrier layer.

[0113] Next, we will explain a different manufacturing method from that shown in Figure 1, using Figure 2. Note that parts are common to both Figure 1 and Figure 2. Since there are many similarities, I will mainly explain the differences. For the common parts, please refer to Figure 1. The explanation can be taken into consideration. Note that in the manufacturing flow shown in Figures 1, 2, and 3, the positive electrode active material is ultimately produced. It states that a quality of 100 can be obtained, but this does not mean that the structure and components will be identical. Rather than being the same, if the manufacturing process is different, at least some parts will be different, for example, particle size, protrusions, concentration The fabric, particle appearance, and other aspects will differ.

[0114] Figure 1 shows the mixture 903 after annealing in step S61, and nickel as an additive source. Although a method for manufacturing by mixing both the source and the aluminum source has been described, one aspect of the present invention is This is not limited to this. As shown in steps S32 and S33 of Figures 2 and 3, there are also other The following additives may be mixed in. The mixing in steps S32 and S33 in Figures 2 and 3 is performed. You may perform crushing beforehand.

[0115] Examples of additive sources include nickel, aluminum, manganese, titanium, and zirconium. Conium, vanadium, iron, chromium, niobium, cobalt, arsenic, zinc, silicon, sulfur, ri One or more elements selected from boron can be used.

[0116] In Figure 2, a zirconium source is used as step S31. Furthermore, as step S32... An example using two types of additives: an aluminum source and a nickel source as step S33. show.

[0117] Methods for mixing these additives include, for example, solid-phase method, sol-gel method, sputtering method, Mechanochemical methods, CVD methods, etc., can be used. Alternatively, multiple methods can be used in combination. It's okay to be there.

[0118] As shown in Figure 2, the nickel source is mixed in step S61-1, and then in step S61- In step 2, the zirconium source and the aluminum source can be mixed. The mixing can be done dry or wet. This can be done using the formula. In this case, for example, step S61-2 can be performed using the sol-gel method. This can be done. When using the sol-gel method, the aluminum source is aluminum alcohol. A side is used, and zirconium alkoxide is used as the zirconium source. Subsequent steps If steps S62, S63, S64, S67, and S68 are performed using the same procedure, the positive electrode active material 100 can be obtained. It can be done.

[0119] Furthermore, the positive electrode immediately after heat treatment of S63 at a heating temperature of 400°C for 2 hours in an oxygen atmosphere. An example of an SEM image of the active material is shown in Figure 5. As shown in Figure 5, after heat treatment at 400°C, on the surface it can be observed that many zirconium oxide particles are attached. Thereafter, the heating temperature in S67 An example of an SEM image of the positive electrode active material immediately after heat treatment is performed at 850°C for 2 hours in an oxidizing atmosphere is shown in Figure 6. As shown in Figure 6, small crystal nuclei (zirconium oxide) after the heat treatment at 400°C undergo crystal growth via the heat treatment at 850°C, and become large lumps (scattered in an island shape). In the positive electrode active material in Figure 6, the zirconium oxide scattered in an island shape functions as a barrier film .

[0120] In addition, instead of dividing into two times under different heating conditions in step S63 and step S67, step S 63 is set as a single heating condition, and an example of an SEM image of the positive electrode active material immediately after heat treatment is performed at 850°C for 2 hours in an oxygen atmosphere is shown in Figure 7. Even when step S63 is set as a single heating condition the zirconium oxide scattered in an island shape functions as a barrier film of the positive electrode active material.

[0121] Further, as shown in Figure 3, LiMO2 and the mixture 902 may be mixed in step S41 and annealed , and then various additive sources may be mixed in step S61. The mixing can be performed by a dry method or a wet method . The annealing conditions can be referred to the description in step S43. The subsequent steps S62, S63, S64, S67, and S68 are performed with the same procedure, whereby the positive electrode active material 100 can be obtained.

[0122] In this manner, by separating the step of introducing the transition metal M and the additive, the profile of each element in the depth direction may be changed in some cases. For example, compared with the central part of the particle the concentration of the additive can be increased in the surface layer part. Further, based on the number of atoms of the transition metal M,​ The ratio of the number of atoms of additive elements to the standard is made higher in the surface layer than in the central layer. It is possible.

[0123] This embodiment can be used in combination with other embodiments.

[0124] (Embodiment 2) In this embodiment, the positive electrode active material particles obtained by the manufacturing method shown in Embodiment 1 are described below. Let me explain. The positive electrode active material particles obtained by the manufacturing method shown in Embodiment 1 are lithium and transition gold It has a layered rock salt-type crystalline structure, which is characteristic of complex oxides containing this group.

[0125] In this specification, etc., the layered rock salt type crystal structure of a composite oxide containing lithium and a transition metal This structure has a rock salt-type ionic arrangement in which cations and anions are arranged alternately, and it contains transition metals and Because lithium is arranged in a regular pattern to form a two-dimensional plane, two-dimensional diffusion of lithium is possible. This refers to the crystal structure. It may contain defects such as vacancies in cations or anions. Also, layers... Strictly speaking, the rock salt crystal structure is a structure in which the lattice of the rock salt crystal is distorted. be.

[0126] Furthermore, in this specification, a rock salt-type crystal structure is defined as a structure in which cations and anions are arranged alternately. This refers to a structure that contains certain elements. It is also acceptable for there to be deficiencies in cations or anions.

[0127] Materials with a layered rock salt-type crystalline structure, such as lithium cobalt oxide (LiCoO2), emit It is known to have high electrical capacity and is excellent as a positive electrode active material for secondary batteries. Examples of materials having a crystalline structure include composite oxides represented by LiMO2.

[0128] The Jahn-Teller effect in transition metal compounds is known to vary in intensity depending on the number of electrons in the d-orbitals of the transition metal, It is known that the intensity of this effect varies depending on the number of electrons in the d-orbitals of the transition metal.

[0129] In compounds containing nickel, distortion is likely to occur due to the Jahn-Teller effect. Therefore, when LiNiO₂ is charged and discharged at a high voltage, there is a concern that the crystal structure may collapse due to the distortion. LiCoO₂ is suggested to have a small Jahn-Teller effect, and may have better resistance to charging and discharging at high voltages, which is preferable. There is a concern that the resulting collapse of the crystal structure may occur. In LiCoO₂, the Jahn-Teller effect is suggested to have a small influence, and it may have superior resistance to charging and discharging at high voltages, which is preferable. The influence is suggested to be small, and the resistance to charging and discharging at high voltages may be more excellent, which is preferable. Good.

[0130] The positive electrode active material will be described with reference to FIGS. 8 to 11. In FIGS. 8 to 11, the case where cobalt is used as the transition metal contained in the positive electrode active material will be described. The case where cobalt is used as the transition metal contained in the positive electrode active material will be described.

[0131] <Conventional Positive Electrode Active Material> The positive electrode active material shown in FIG. 10 is lithium cobalt oxide (LiCoO₂) to which halogen and magnesium are not added by the production method described later. The lithium cobalt oxide shown in FIG. 10 changes its crystal structure depending on the charging depth, as described in Non-Patent Document 1, Non-Patent Document 2, and the like. As described in Non-Patent Document 1, Non-Patent Document 2, etc., the crystal structure changes depending on the charging depth. changes.

[0132] As shown in FIG. 10, lithium cobalt oxide at a charging depth of 0 (discharged state) has a region with a crystal structure of space group R-3m, and three CoO₂ layers exist in the unit cell. has a region with a crystal structure of space group R-3m, and three CoO₂ layers exist in the unit cell. Therefore, this crystal structure is sometimes referred to as an O3-type crystal structure. Note that the CoO₂ layer refers to a structure in which octahedral structures each having cobalt coordinated with 6 oxygen atoms are continuously connected in a plane in a state of shared edges. refers to a structure in which octahedral structures each having cobalt coordinated with 6 oxygen atoms are continuously connected in a plane in a state of shared edges. is defined as such.

[0133] Furthermore, when the charging depth is 1, it has a crystal structure of space group P-3m1, and the unit cell contains Co One O2 layer is present. Therefore, this crystal structure is sometimes called an O1 type crystal structure.

[0134] Furthermore, lithium cobalt oxide at a charge depth of approximately 0.88 has a crystal structure of space group R-3m. It has a structure. This structure has a CoO2 structure like P-3m1(O1) and R-3m(O 3) It can also be described as a structure in which LiCoO2 structures like this are alternately stacked. The crystal structure is sometimes called the H1-3 type crystal structure. In this structure, the number of cobalt atoms per unit cell is twice that of other structures. However, Figure 1 In this specification, starting with 0, the c-axis of the H1-3 type crystal structure is used to facilitate comparison with other structures. The diagram will be shown as a representation of half the size of a unit cell.

[0135] As an example, the H1-3 type crystal structure is described in Non-Patent Document 2, where the unit cell The coordinates of cobalt and oxygen are given as follows: Co(0, 0, 0.42150±0.00016), O 1(0, 0, 0.27671±0.00045), O2(0, 0, 0.11535±0. It can be expressed as 00045). O1 and O2 are oxygen atoms, respectively. The H1-3 type crystal structure is represented by a unit cell consisting of one cobalt and two oxygen atoms. On the other hand, as will be described later, the O3' type crystal structure of one aspect of the present invention is preferably one It is represented by a unit cell using cobalt and one oxygen atom. This is an O3' type crystal structure. In the case of the O3' type structure, the symmetry between cobalt and oxygen differs from that of the H1-3 type structure, and the O3' type structure is formed. The crystalline structure shows less variation from the O3 structure compared to the H1-3 type structure. (Positive electrode) Which unit cell is more preferable for representing the crystal structure of the active material? For example, in Rietveld analysis of XRD, GOF (good of fit) You should choose the option that makes the value of ss smaller.

[0136] High-voltage charging such that the charging voltage is 4.6V or higher based on the oxidation-reduction potential of lithium metal. If you repeatedly charge to a deep depth of 0.8 or more, and then discharge the battery, Lithium cobalt oxide has an H1-3 type crystal structure and a R-3m(O3) structure in its discharged state. During this process, the crystal structure undergoes repeated changes (i.e., non-equilibrium phase transitions).

[0137] However, these two crystal structures show a large displacement of the CoO2 layer. (See dotted line in Figure 10) And as indicated by the arrows, in the H1-3 type crystal structure, the CoO2 layer is large from R-3m(O3) It is collapsing. Such dynamic structural changes negatively affect the stability of the crystal structure. Eur.

[0138] Furthermore, the volume difference is also large. When comparing per the same number of cobalt atoms, H1-3 type crystal The difference in volume between the structure and the O3-type crystal structure in the discharged state is 3.0% or more.

[0139] In addition, the H1-3 type crystal structure has a continuous CoO2 layer, such as P-3m1(O1). The resulting structure is likely to be unstable.

[0140] Therefore, repeated high-voltage charging and discharging causes the crystalline structure of lithium cobalt oxide to break down. The breakdown of the crystal structure causes a deterioration in cycle properties. This reduces the number of sites where lithium can exist stably, and also makes lithium insertion and removal more difficult. This is likely the reason.

[0141] <Cathode active material> In one aspect of the present invention, the positive electrode active material undergoes repeated high-voltage charging and discharging, and the CoO2 layer This can be made smaller. Furthermore, the change in volume can be made smaller. Therefore, A positive electrode active material according to one aspect of the present invention can achieve excellent cycle characteristics. A positive electrode active material according to one aspect of the invention can adopt a stable crystalline structure in a high-voltage charged state. In one embodiment of the present invention, the positive electrode active material maintains a high-voltage charge state, In some cases, a reaction may be less likely to occur. In such cases, safety is further improved, which is preferable. .

[0142] In one embodiment of the present invention, the positive electrode active material is in a fully discharged state and a high-voltage charged state. In this case, the difference in volume when comparing the change in crystal structure and the same number of transition metal atoms is small.

[0143] Figure 8 shows the crystal structure of the positive electrode active material before and after charging and discharging. The positive electrode active material is lithium and transition gold. It is a composite oxide having cobalt and oxygen as genus M. In addition to the above, as an additive It is preferable that the material contains magnesium, aluminum, nickel, titanium, and zirconium. Furthermore, it is preferable to have halogens such as fluorine, chlorine, and bromine as additives.

[0144] The crystal structure at charge depth 0 (discharge state) in Figure 8 is R-3m(O3), the same as in Figure 10. On the other hand, the positive electrode active material has a different crystal structure than the H1-3 type when fully charged to a certain depth of charge. It has a crystalline structure. This structure has a space group R-3m and is not a spinel-type crystalline structure. In this system, ions such as cobalt and magnesium occupy the 6-coordinate position of oxygen, and the arrangement of cations is such that It has symmetry similar to the Pinel type. Furthermore, the periodicity of the CoO2 layer in this structure is the same as that of the O3 type. Therefore, in this specification, this structure is referred to as an O3' type crystal structure, or a pseudo-spinel type crystal structure. Therefore, the O3' type crystal structure can be rephrased as the pseudo-spinel type crystal structure. Good. Note that in the crystal structure diagram of the O3' type crystal structure shown in Figure 8, the cobalt atoms In order to explain the symmetry and the symmetry of the oxygen atom, the representation of lithium has been omitted, In reality, lithium exists between the CoO2 layers at a concentration of, for example, less than 20 atoms relative to cobalt. Furthermore, in both the O3-type and O3'-type crystal structures, the CoO2 layer It is preferable that a dilute amount of magnesium be present in between, that is, at the lithium site. It is preferable that halogens such as fluorine are present randomly and dilutely at the oxygen sites.

[0145] Furthermore, in the O3' type crystal structure, light elements such as lithium may occupy the oxygen 4-coordinate position. In this case as well, the arrangement of ions has a symmetry similar to that of the spinel type.

[0146] Furthermore, the O3' type crystal structure is a CdCl2 type crystal, although it has Li randomly placed between the layers. It can also be said that it is a crystal structure similar to the structure. This crystal structure similar to the CdCl2 type The manufacturing process is as follows: When lithium nickel oxide is charged to a charging depth of 0.94 (Li 0.06 NiO2 Its crystal structure is similar to that of ), but it is pure lithium cobaltate, or layered rock salt rich in cobalt. It is known that this crystal structure is not typically adopted in cathode active materials of this type.

[0147] In one embodiment of the present invention, when a large amount of lithium is released during high-voltage charging, Changes in the crystal structure are suppressed compared to conventional cathode active materials. For example, as shown by the dotted line in Figure 8. As such, there is almost no displacement of the CoO2 layer in these crystal structures.

[0148] More specifically, the positive electrode active material of one aspect of the present invention maintains its structure even when the charging voltage is high. It has high stability. For example, in conventional positive electrode active materials, the charging electrode has an H1-3 type crystal structure. Even at a voltage of approximately 4.6V, for example, with the potential of lithium metal as the reference, R-3m(O 3) There exists a region of charging voltage in which the crystal structure can be maintained, and further, a region where the charging voltage is increased, for example For example, even at a voltage of about 4.65V to 4.7V relative to the potential of lithium metal, O3 There is a region where a 'type crystal structure can be adopted. Furthermore, when the charging voltage is increased, H1-3 finally appears. In some cases, crystal structures may be observed. Furthermore, in secondary batteries, for example, graphite is used as the negative electrode active material. When using it, for example, even if the voltage of the secondary battery is between 4.3V and 4.5V, R-3m There is a region of charging voltage in which the crystal structure of (O3) can be maintained, and a region where the charging voltage is further increased. For example, even when the potential of lithium metal is between 4.35V and 4.55V, O3 There is a region where a 'type crystal structure can be adopted.

[0149] Therefore, in the positive electrode active material of one aspect of the present invention, even if charging and discharging are repeated at high voltage, The crystal structure is less likely to collapse.

[0150] Furthermore, the positive electrode active material exhibits an O3-type crystal structure with a charging depth of 0 and an O3'-type crystal structure with a charging depth of 0.88. The volume difference per unit cell in the crystal structure is less than 2.5%, more specifically less than 2.2%. ru.

[0151] In the O3' type crystal structure, the coordinates of cobalt and oxygen in the unit cell are Co(0, This can be shown within the range 0,0.5, O(0,0,x), and 0.20≦x≦0.25. .

[0152] Additives that are randomly and dilutely present between the CoO2 layers, i.e., at the lithium sites, for example, ma Magnesium has the effect of suppressing the displacement of the CoO2 layer. Therefore, magnesium between the CoO2 layers The presence of cilium makes it easier to form an O3' type crystal structure. Therefore, magnesium is used in the present invention. It is preferable that magnesium is distributed throughout the particles of the positive electrode active material in one embodiment. In order to distribute it throughout, in the process of preparing the positive electrode active material according to one embodiment of the present invention, a heat treatment is performed. It is preferable to do so.

[0153] However, if the heat treatment temperature is too high, cation mixing occurs, affecting the additives, for example. For example, the likelihood of magnesium entering cobalt site increases. Gnesium does not have the effect of maintaining the R-3m structure during high-voltage charging. Furthermore, heating treatment If the temperature is too high, the cobalt will be reduced to its divalent state, and the lithium will evaporate. Other negative consequences are also a concern.

[0154] Therefore, prior to the heat treatment to distribute magnesium throughout the particles, cobalt acid It is preferable to add halogen compounds such as fluorine compounds to lithium. Adding a substance causes a decrease in the melting point of lithium cobalt oxide. By lowering the melting point, the At temperatures where on-mixing is unlikely to occur, it is easy to distribute magnesium throughout the particles. It is. Furthermore, if a fluorine compound is present, it provides corrosion resistance to hydrofluoric acid produced by the decomposition of the electrolyte. It can be expected that this will improve.

[0155] Furthermore, increasing the magnesium concentration beyond the desired value reduces its effect on stabilizing the crystal structure. In some cases, this can occur. Magnesium, in addition to lithium sites, also contains cobalt sites. This is thought to be because it will also be able to enter the to The number of um atoms is preferably 0.001 times or more and 0.1 times or less the number of transition metal M atoms, and 0. A value greater than 0.01 and less than 0.04 is more preferable, and around 0.02 is even more preferable. The magnesium concentration can be determined, for example, by measuring the elemental content of the entire particle of the positive electrode active material using ICP-MS. The values ​​may be those obtained through analysis, or they may be based on the raw material composition values ​​during the process of manufacturing the positive electrode active material. It's okay to be there.

[0156] Lithium cobalt oxide can be used with a metal other than cobalt (hereinafter referred to as metal Z), for example, nickel. One or more metals selected from aluminum, manganese, titanium, vanadium, and chromium It may be added, and it is particularly preferable to add one or more nickel and aluminum. Manganese, titanium, vanadium, and chromium can sometimes be stable in the tetravalent state, and structure In some cases, it contributes significantly to stability. By adding metal Z, the positive electrode activity of one aspect of the present invention In materials, for example, the crystal structure may become more stable under high-voltage charging conditions. In this embodiment of the present invention, in a positive electrode active material, metal Z is the crystalline property of lithium cobalt oxide. It is preferable to add it at a concentration that does not change significantly. For example, the aforementioned Yarn Terra - It is preferable that the amount is such that it does not produce any effect.

[0157] As shown in the legend in Figure 8, transition metals such as nickel and manganese, and aluminum While it is preferable for nium to be present in the cobalt site, some of it is present in the lithium site. It may be present. Furthermore, magnesium is preferably present at the lithium site. Oxygen is present at one The part may be substituted with fluorine.

[0158] As the magnesium concentration of the positive electrode active material in one aspect of the present invention increases, the volume of the positive electrode active material The amount may decrease. One possible reason for this is the entry of magnesium into the lithium site. This could potentially reduce the amount of lithium that contributes to charging and discharging. In some cases, magnesium may produce magnesium compounds that do not contribute to charging and discharging. (This invention) In one embodiment, the positive electrode active material contains nickel as metal Z in addition to magnesium. Furthermore, it may be possible to increase the capacity per unit weight and per unit volume. In one embodiment, the positive electrode active material has aluminum as the metal Z in addition to magnesium. In some cases, the capacity per unit weight and per unit volume can be increased. One embodiment of the positive electrode active material has nickel and aluminum in addition to magnesium. This can sometimes increase the capacity per unit weight and per unit volume.

[0159] The concentrations of elements such as magnesium and metal Z in the positive electrode active material according to one embodiment of the present invention are as follows: This is expressed using the number of atoms.

[0160] The number of nickel atoms in the positive electrode active material according to one aspect of the present invention is 10% of the number of cobalt atoms. The following are preferred, more preferably 7.5% or less, and even more preferably 0.05% to 4%. A nickel concentration of 0.1% to 2% is particularly preferred. The nickel concentration shown here is, for example, ICP -This may be a value obtained by elemental analysis of the entire particle of the positive electrode active material using MS, etc. It may also be based on the values ​​of the raw material composition during the process of manufacturing the substance.

[0161] When a high-voltage charge is maintained for a long period of time, transition metals dissolve from the positive electrode active material into the electrolyte. This may cause the crystal structure to collapse. However, by having nickel in the above proportion, the positive electrode activity In some cases, it is possible to suppress the leaching of transition metals from materials.

[0162] The number of aluminum atoms in the positive electrode active material according to one aspect of the present invention is equal to the number of cobalt atoms. A is preferably between 0.05% and 4%, and more preferably between 0.1% and 2%. Hereinafter, A The luminium concentration can be determined, for example, by elemental analysis of the entire particle of the positive electrode active material using ICP-MS. It may be a value obtained by the process, or it may be based on the values ​​of the raw material composition during the manufacturing process of the positive electrode active material. That's good too.

[0163] If the electrolyte contains LiPF6, hydrolysis may generate hydrogen fluoride. Furthermore, hydrogen fluoride is produced by the reaction of PVDF, which is used as a component of the positive electrode, with alkali. This can also occur. A decrease in the hydrogen fluoride concentration in the charge solution can lead to corrosion of the current collector. , and / or it may be possible to suppress peeling of the coating. Also, gelation of PVDF, and / or In some cases, this can suppress the decrease in adhesiveness due to insolubilization.

[0164] In one embodiment of the present invention, when the positive electrode active material contains magnesium in addition to element X, high voltage charging It has extremely high stability in the electrical state. If element X is phosphorus, the number of phosphorus atoms is equal to the number of cobalt atoms. Preferably, the amount of atoms is 1% to 20%, more preferably 2% to 10%, and 3% More preferably, the amount is 8% or less, and in addition, the number of magnesium atoms is 0 times the number of cobalt atoms. Preferably between 0.1% and 10%, more preferably between 0.5% and 5%, and 0.7% or more. A concentration of 4% or less is more preferable. The phosphorus and magnesium concentrations shown here are, for example, ICP- The values ​​may be those obtained by elemental analysis of the entire particle of the positive electrode active material using MS, etc. The quality may also be based on the values ​​of the raw material composition during the manufacturing process.

[0165] If the positive electrode active material has cracks, phosphorus, more specifically phosphorus and acid may be present inside. The presence of compounds containing certain elements can sometimes inhibit the progression of cracks.

[0166] <Surface layer> Magnesium is distributed throughout the particles of the positive electrode active material according to one embodiment of the present invention. This is preferable, but in addition, the magnesium concentration in the surface layer a is higher than the average of the entire particle. This is preferable. For example, the magnesium concentration in the surface layer measured by XPS, etc., is ICP-M It is preferable that the magnesium concentration is higher than the average magnesium concentration of the entire particle measured by S, etc.

[0167] Furthermore, in one embodiment of the present invention, the positive electrode active material may be an element other than cobalt, such as nickel, aluminum, etc. In the case where there is one or more metals selected from um, manganese, iron and chromium, the gold It is preferable that the concentration near the surface of the particles is higher than the average concentration of the entire particle. For example, The concentrations of elements other than cobalt in the surface layer, as measured by XPS, etc., are measured by ICP-MS, etc. It is preferable that the concentration of the element is higher than the average concentration of the entire set of particles.

[0168] The surface of each particle is, in a sense, entirely composed of crystal defects, and lithium leaks from the surface during charging. Because of this, the lithium concentration tends to be lower in this area than in the interior. Therefore, it becomes unstable. This is a region where the crystal structure is easily broken down. If the magnesium concentration in the surface layer is high, the crystal Structural changes can be suppressed more effectively. Also, the magnesium concentration in the surface layer is high. Furthermore, it can be expected that the corrosion resistance to hydrofluoric acid produced by the decomposition of the electrolyte will improve.

[0169] Furthermore, the concentration of halogens such as fluorine in the surface layer of the positive electrode active material according to one aspect of the present invention is also the same as the concentration of the entire particle. It is preferable that the average value is higher than the average. Halogens are present in the surface layer, which is the region in contact with the electrolyte. This effectively improves corrosion resistance to hydrofluoric acid.

[0170] Thus, the surface layer of the positive electrode active material in one aspect of the present invention is more concentrated than the interior due to additives, such as magnesium. It is preferable that the concentration of citric acid and fluorine is high, and that the composition differs from that of the interior. It is preferable that the resulting material adopts a crystalline structure that is stable at room temperature. Therefore, the surface layer is different from the interior. It may have a crystalline structure. For example, at least the surface layer a of the positive electrode active material in one aspect of the present invention It may also have a rock salt-type crystalline structure in part. Furthermore, the surface and interior may have different crystalline structures. If this is present, it is preferable that the orientation of the crystals in the surface layer and the interior are roughly the same.

[0171] Layered rock salt crystals, and the anions of rock salt crystals, have a cubic close-packed structure (face-centered cubic lattice structure). ) takes the form of. It is also presumed that in O3' type crystals, the anions take the form of a cubic close-packed structure. These are When in contact, there exists a crystal plane in which the orientation of the cubic close-packed structure composed of anions is aligned. However, the space group of layered rock salt crystals and O3'-type crystals is R-3m, and the space group of rock salt crystals is R-3m. The space groups Fm-3m (the space group of typical rock salt crystals) and Fd-3m (the simplest symmetry) Because it is different from the space group of rock salt-type crystals having the above conditions, the Miller indices of crystal planes satisfying the above conditions These differ between layered rock salt crystals and O3'-type crystals, and in rock salt crystals, they are different. In this specification, layered rock In salt-type crystals, O3'-type crystals, and rock salt-type crystals, the cubic ions are composed of anions. When the orientations of the densely packed structures are aligned, it can be said that the crystal orientations are roughly consistent.

[0172] The approximate agreement of the crystal orientation in the two regions can be seen in TEM (transmission electron microscope) images and STE (spherical spectroscopy) images. M (Scanning Transmission Electron Microscope) image, HAADF-STEM (High-angle scattering annular dark-field scanning transmission electron microscope) image. The determination should be made based on images from a microscope, ABF-STEM (annular bright-field scanning transmission electron microscope), etc. This can be done. X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. can also be used as criteria for judgment. Yes, it is possible. If the crystal orientation is roughly consistent, cations and anions can be seen in a linear fashion in TEM images, etc. The difference in direction between the alternating rows is 5 degrees or less, more preferably 2.5 degrees or less. It can be inferred. However, light elements such as oxygen and fluorine cannot be clearly observed in TEM images, etc. In some cases, however, the alignment of the metal elements can be determined by their arrangement.

[0173] However, if the surface layer consists only of MgO, or only of a solid solution of MgO and CoO(II), The insertion and removal of lithium becomes difficult. Therefore, the surface layer contains at least cobalt. In the discharge state, it also contains lithium and must have a path for lithium insertion and removal. Furthermore, it is preferable that the concentration of cobalt is higher than that of magnesium.

[0174] ≪Particle Size≫ In one embodiment of the present invention, if the particle size of the positive electrode active material is too large, lithium diffusion becomes difficult. There are problems such as the surface of the active material layer becoming too rough when coated onto the current collector. If the size is too small, it becomes difficult to support the active material layer when coating the current collector, and the reaction with the electrolyte becomes excessive. Problems such as the progression to [a certain stage] also arise. Therefore, the average particle diameter (D50: also called the median diameter) However, a size of 1 μm to 100 μm is preferred, and a size of 2 μm to 40 μm is more preferred. More preferably, the particle size is between 5 μm and 30 μm.

[0175] <Analysis method> One embodiment of the present invention involves a positive electrode active material that exhibits an O3' type crystal structure when charged at a high voltage. Whether or not a material is a positive electrode active material can be determined by XRD, electron diffraction, and neutron beam diffraction on a positive electrode charged with high voltage. This can be determined by analyzing the data using diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. Yes, it is possible. In particular, XRD can determine the symmetry of transition metals such as cobalt in the positive electrode active material with high resolution. It can analyze the crystallinity and crystal orientation, and compare the periodic strain and crystal structure of the lattice. Even if you measure the positive electrode obtained by disassembling a secondary battery directly, you can perform analysis at the Akiko size, and the measurement will be sufficiently accurate. It is preferable in that it allows for obtaining a certain degree of performance.

[0176] The positive electrode active material according to one aspect of the present invention is in a state when charged at a high voltage and when discharged, as described above. A characteristic feature is that there is little change in the crystal structure when charged at high voltage and when discharged. Materials in which the crystal structure with large changes accounts for more than 50 wt% cannot withstand high-voltage charging and discharging. Therefore, it is undesirable. Furthermore, simply adding additive elements does not guarantee that the desired crystal structure will be achieved. It is important to note that there are combinations. For example, cobalt acids containing magnesium and fluorine. Although they share the common characteristic of being lithium, when charged at high voltage, the O3' type crystal structure is 60 There are cases where the percentage exceeds wt%, and cases where the H1-3 type crystal structure accounts for 50 wt% or more. Furthermore, at a predetermined voltage, the O3' type crystal structure becomes approximately 100 wt%, and furthermore, the predetermined In some cases, increasing the voltage can result in the formation of an H1-3 type crystal structure. Therefore, in one aspect of the present invention To determine whether or not it is a positive electrode active material, analysis of its crystal structure, including XRD, is necessary. It is necessary.

[0177] However, when the positive electrode active material is in a high-voltage charged or discharged state, its crystalline structure changes when exposed to the air. Changes in structure can occur. For example, a change from an O3' type crystal structure to an H1-3 type crystal structure may occur. This may occur. Therefore, all samples should be handled in an inert atmosphere such as an argon atmosphere. It is preferable to do so.

[0178] <Charging Method> To determine whether a certain composite oxide is a positive electrode active material according to one aspect of the present invention High-voltage charging is used, for example, with a lithium counter electrode coin cell (CR2032 type, 20mm diameter). A device with a height of 3.2 mm can be manufactured and charged.

[0179] More specifically, the positive electrode consists of a slurry mixed with positive electrode active material, a conductive additive, and a binder. A positive electrode current collector made of aluminum foil can be used, coated with this material.

[0180] Lithium metal can be used as the counter electrode. However, if a material other than lithium metal is used as the counter electrode... When this occurs, the potential of the secondary battery and the potential of the positive electrode are different. Voltage and potential in this specification, etc. Unless otherwise specified, this represents the potential of the positive electrode.

[0181] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluoride phosphate (LiPF6). The electrolyte used is ethylene carbonate (EC) and diethyl carbonate (DEC). EC:DEC = 3:7 (volume ratio), vinylene carbonate (VC) is mixed at 2 wt%. You can use the one that you have.

[0182] Polypropylene with a thickness of 25 μm can be used for the separator.

[0183] The positive electrode and negative electrode cans can be made of stainless steel (SUS). Cut.

[0184] The coin cell manufactured under the above conditions was charged with a constant current of 4.6V and 0.5C, and then the current value was measured. Charge at a constant voltage until the current reaches 0.01C. Here, 1C is defined as 137mA / g. The temperature should be set to 25°C. After charging in this manner, the coin cell is subjected to an argon atmosphere glow. By disassembling the device in a box and removing the positive electrode, a positive electrode active material charged with high voltage can be obtained. To suppress reactions with external components when performing various analyses afterward, the area is sealed in an argon atmosphere. It is preferable to do so. For example, XRD can be performed by sealing the sample in a sealed container under an argon atmosphere. can.

[0185] ≪XRD≫ CuKα calculated from the O3' type crystal structure and H1-3 type crystal structure models. Figures 9 and 11 show ideal powder XRD patterns using a single line. For comparison, a charged XRD pattern is also shown. The crystal structure of LiCoO2(O3) at depth 0 and CoO2(O1) at charging depth 1 was calculated. The ideal XRD pattern is also shown. Note that LiCoO2(O3) and CoO2(O1 The pattern is ICSD (Inorganic Crystal Structure). From the crystal structure information obtained from the Database (see Non-Patent Document 5), Reflex Pow is one of the modules in ls Studio (BIOVIA). The graph was created using der Diffraction. The range of 2θ was set from 15° to 75°. , Step size=0.01, wavelength λ1=1.540562×10 -10 m, λ2 is No settings were specified, and Monochromator was set to single. The H1-3 type crystal structure was... The turns were similarly created from the crystal structure information described in Non-Patent Document 3. The crystal structure pattern is estimated from the XRD pattern of the positive electrode active material according to one embodiment of the present invention. Using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), We then performed the necessary adjustments and created an XRD pattern, similar to the others.

[0186] As shown in Figure 9, in the O3' type crystal structure, 2θ = 19.30 ± 0.20° (19.1 (0° to 19.50°), and 2θ = 45.55 ± 0.10° (45.45° or more) Diffraction peaks appear below 45.65°. More specifically, 2θ = 19.30 ± 0.10° (between 19.20° and 19.40°), and 2θ = 45.55 ± 0.05 A sharp diffraction peak appears at 45.50° to 45.60°. However, as shown in Figure 11... As such, in the H1-3 type crystal structure and CoO2 (P-3m1, O1), pins are present at these positions. No curve appears. Therefore, when charged at high voltage, 2θ = 19.30 ± 0.20° The appearance of a peak at 2θ = 45.55 ± 0.10° is in accordance with one aspect of the present invention. This can be considered a characteristic of highly active materials.

[0187] This shows the crystal structure at a charging depth of 0 and the crystal structure when charged at high voltage, and the XRD diffraction peak It can also be said that the locations where the peaks appear are close together. More specifically, the main diffraction peaks of both. In two or more of these, more preferably three or more, the difference in the position where the peak appears is 2θ It can be said that 2θ = 0.7 or less, and more preferably 2θ = 0.5 or less.

[0188] Furthermore, the positive electrode active material according to one embodiment of the present invention has an O3' type crystal structure when charged with a high voltage. However, not all particles have to have an O3'-type crystal structure. Other crystal structures may also be present. Furthermore, a portion may be amorphous. However, Rietveld analysis of the XRD pattern is performed. When this is done, it is preferable that the O3' type crystal structure is 50 wt% or more, and preferably 60 wt% or more. It is more preferable that the content be 66 wt% or more. O3' type crystal The structure is 50 wt% or more, more preferably 60 wt% or more, and even more preferably 66 wt% or less. If the above is achieved, it can be made into a positive electrode active material with sufficiently excellent cycle characteristics.

[0189] Furthermore, Rietveld analysis was performed even after more than 100 charge-discharge cycles from the start of measurement. When the O3' type crystal structure is present, it is preferable that it is 35 wt% or more, and preferably 40 wt% or more. This is more preferable, and even more preferable is 43 wt% or more.

[0190] Furthermore, the crystallite size of the O3'-type crystal structure possessed by the particles of the positive electrode active material is determined by the discharge state of Li It only drops to about 1 / 10th of the CoO2(O3) level. Therefore, it is the same as the positive electrode before charging and discharging. Even under XRD measurement conditions, a clear peak of the O3' type crystal structure was observed after high-voltage charging. On the other hand, in simple LiCoO2, some parts can take on a structure similar to the O3' type crystal structure. However, the crystallite size becomes smaller, and the peaks become broader and smaller. The crystallite size is X It can be calculated from the full width at half maximum of the RD peak.

[0191] Furthermore, in this specification, the theoretical capacity of the positive electrode active material refers to the insertable and removable capacity of the positive electrode active material. This refers to the amount of electricity that would be generated if all lithium were to be desorbed. For example, the theoretical capacity of LiCoO2 is 274. In mAh / g, the theoretical capacity of LiNiO2 is 274mAh / g, and the theoretical capacity of LiMn2O4 is It is 148mAh / g.

[0192] Furthermore, in this specification, etc., the charging depth when all insertable and removable lithium is inserted. Let 0 be the charge depth when all the insertable and detachable lithium in the positive electrode active material has been detached, and 1 be the charge depth when 0 is the charge depth when 1 is the charge depth when all the insertable and detachable lithium in the positive electrode active material has been detached. This is what is meant. Also, the positive electrode active material with a charge depth of 0.7 to 0.9 is charged with a high voltage. It is sometimes called a positive electrode active material. Also, a positive electrode active material with a charge depth of 0.06 or less, or high The positive electrode active material, which has been discharged to more than 90% of its charge capacity from a state where it was charged by voltage, is sufficiently... This refers to the discharged positive electrode active material.

[0193] The discharge rate is the relative ratio of the current during discharge to the battery capacity, and is expressed in units of C. In a battery with a rated capacity of X (Ah), the current equivalent to 1C is X (A). 2X(A) If the discharge is performed with a current of ), it is said that the discharge was performed at 2C, and if the discharge is performed with a current of X / 5(A) In that case, it was discharged at 0.2C. The charging rate was also the same, 2X(A). When it is charged with current, it is said to have been charged at 2C, and when it is charged with a current of X / 5(A) He said he charged it at 0.2C.

[0194] Constant current charging refers to a method of charging while maintaining a constant charging rate. Constant voltage charging is... For example, this refers to a method of charging where the voltage is kept constant once the upper voltage limit is reached. "Electricity" refers, for example, to a method of performing discharge while maintaining a constant discharge rate.

[0195] Furthermore, in this specification, a value in the vicinity of a certain numerical value A is defined as a value between 0.9A and 1.1A. Let's leave it at that.

[0196] Furthermore, in this specification, etc., a secondary battery using a positive electrode and positive electrode active material according to one aspect of the present invention Although examples sometimes show lithium metal being used as the counter electrode, one embodiment of the present invention is a secondary battery that uses lithium metal. This invention is not limited to this. Other materials, such as graphite or lithium titanate, may be used for the negative electrode. A positive electrode and positive electrode active material in one embodiment, which have a crystal structure that does not easily collapse even after repeated charging and discharging, and are of good quality. Properties such as obtaining desirable cycle characteristics are not affected by the negative electrode material. Furthermore, in one aspect of the present invention... Regarding secondary batteries, the charging voltage is higher than the typical charging voltage of around 4.7V for lithium counter electrodes. While examples of charging and discharging at high voltages are sometimes shown, charging and discharging at lower voltages is also acceptable. When charging and discharging at high voltage, the cycle characteristics will be even better than those shown in this specification. It is expected.

[0197] (Embodiment 3) In this embodiment, regarding a lithium-ion secondary battery containing a positive electrode active material according to one aspect of the present invention Let me explain. A secondary battery consists of an outer casing, a current collector, an active material (positive electrode active material or negative electrode active material), and a conductor. It contains at least an electrolytic agent and a binder. It also contains an electrolytic agent containing a lithium salt or the like. It contains a liquid. In the case of a secondary battery that uses an electrolyte, there is a positive electrode, a negative electrode, and a space between the positive and negative electrodes. A pallet is provided.

[0198] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer is as shown in Embodiment 1. It is preferable to have a positive electrode active material 100, and even if it has a binder, conductive additive, etc. good.

[0199] Figure 12(A) shows an example of a schematic diagram of the cross-section of the positive electrode.

[0200] The current collector 550 is a metal foil, and by applying slurry to the metal foil and drying it, positive The electrodes are formed. After drying, further pressing may be applied. The positive electrode is active on the current collector 550. It is a material layer that has been formed.

[0201] Slurry is a material liquid used to form an active material layer on the current collector 550, and is less than The mixture contains at least an active material, a binder, and a solvent, and preferably further contains a conductive additive. It refers to a substance that has been used for electrodes. Slurries are sometimes also called electrode slurries or active material slurries. When forming the positive electrode active material layer, use a slurry for the positive electrode, and when forming the negative electrode active material layer, It is sometimes called a slurry for the negative electrode.

[0202] Conductive additives, also called conductive imparters or conductive materials, are made of carbon materials. By attaching a conductive additive, multiple active materials are electrically connected to each other, increasing conductivity. Furthermore, "adhesion" refers only to the physical close contact between the active material and the conductive additive. Rather, when covalent bonding occurs, when bonding occurs by van der Waals forces, the active material When a conductive additive covers a portion of the surface, or when the conductive additive fits into the surface irregularities of the active material, This concept includes cases where there is no direct physical contact but there is an electrical connection.

[0203] A typical example of a carbon material used as a conductive additive is carbon black (furnace (These include black, acetylene black, graphite, etc.)

[0204] Figure 12(A) shows acetylene black 553 as a conductive additive. In 12(A), a second active material having a smaller particle size than the positive electrode active material 100 shown in Embodiment 1 is used. This shows an example of mixing quality 562. Mixing particles of different sizes results in a high density. It can be used as the positive electrode active material layer, thereby increasing the charge and discharge capacity of the secondary battery. The positive electrode active material 100 shown in Embodiment 1 corresponds to the active material 561 in Figure 12(A).

[0205] To fix the current collector 550, such as metal foil, to the active material as the positive electrode of a secondary battery, A binder (resin) is mixed in. The binder is also called a binding agent. The binder is a polymer material. It is a material, and if a lot of binder is included, the proportion of active material in the positive electrode decreases, and the secondary battery The discharge capacity decreases. Therefore, the amount of binder mixed in is kept to a minimum. Figure 12(A) It is filled with active material 561, second active material 562, and acetylene black 553. The area refers to a void or binder.

[0206] Note that Figure 12(A) shows an example in which the active material 561 is depicted as a sphere, but there are no particular limitations. It is not limited to a specific shape, and can be in various forms. The cross-sectional shape of the active material 561 may be elliptical, rectangular, trapezoidal, It can be a cone shape, a quadrilateral with rounded corners, or an asymmetrical shape.

[0207] Figure 12(B) shows examples of the active material 561 being illustrated in various shapes. Figure 2(B) shows a different example from Figure 12(A).

[0208] Furthermore, in the positive electrode of Figure 12(B), graphene is used as the carbon material used as a conductive additive. 554 is being used.

[0209] Graphene possesses remarkable electrical, mechanical, or chemical properties, therefore graphene This carbon material is expected to have applications in various fields, such as field-effect transistors and solar cells. be.

[0210] Figure 12(B) shows the active material 561, graphene 554, and acetylene black on the current collector 550. A positive electrode active material layer having 553 is formed.

[0211] Furthermore, the process involves mixing graphene 554 and acetylene black 553 to obtain an electrode slurry. In this case, the weight of the carbon black to be mixed should be between 1.5 and 20 times the weight of the graphene. It is preferable that the weight be between 2 and 9.5 times the original weight.

[0212] Furthermore, if the mixture of graphene 554 and acetylene black 553 is defined as the above range, then the slurry - During preparation, acetylene black 553 exhibits excellent dispersion stability, making it less likely to form aggregates. If the above range is defined as a mixture of graphene 554 and acetylene black 553, then acetylene It is possible to achieve a higher electrode density than a positive electrode using only Black 553 as a conductive additive. By increasing the extreme density, the volume per unit weight can be increased. Specifically, Furthermore, the density of the positive electrode active material layer, as measured by weight, can be higher than 3.5 g / cc. Furthermore, the positive electrode active material 100 shown in Embodiment 1 is used as the positive electrode, and graphene 554 and If the mixture of cetylene black 553 is within the above range, the secondary battery will have a higher capacity. Therefore, a synergistic effect can be expected, which is desirable.

[0213] Furthermore, compared to a positive electrode using only graphene as a conductive additive, the electrode density is lower, but the first carbon The mixture of the material (graphene) and the second carbon material (acetylene black) is defined as being within the above range. This enables rapid charging. Also, the positive electrode active material 100 shown in Embodiment 1 The positive electrode is used, and a mixture of graphene 554 and acetylene black 553 is used within the above range. This synergistically leads to increased stability of the secondary battery and the ability to support even faster charging. It is desirable as it is expected to be effective.

[0214] These features make it effective as a secondary battery for use in vehicles.

[0215] Increasing the number of secondary batteries increases the weight of the vehicle, which in turn increases the energy required to move it. The cruising range will also be shorter. By using high-density secondary batteries, the same weight of secondary batteries can be mounted. The driving range can be maintained with virtually no change in the vehicle's total weight.

[0216] Furthermore, as the capacity of a vehicle's secondary battery increases, more power is required for charging, so charging is done in a short time. It is desirable to terminate this. Also, when the vehicle brakes are applied, it is desirable to temporarily generate electricity. Because charging is performed under high-rate charging conditions during so-called regenerative charging, Good rate characteristics are required for secondary batteries used in vehicles.

[0217] The positive electrode active material 100 shown in Embodiment 1 is used as the positive electrode, and acetylene black and gra By optimizing the mixing ratio of the fen, it is possible to achieve high electrode density and appropriate gaps necessary for ion conduction. This makes it possible to create a balance between the two, resulting in an automotive system with high energy density and good output characteristics. A rechargeable battery can be obtained for this purpose.

[0218] Furthermore, this configuration is also effective in portable information terminals, and the positive electrode active material 1 shown in Embodiment 1 By using 00 as the positive electrode and adjusting the mixing ratio of acetylene black and graphene to an optimal range. This allows for miniaturization and increased capacity of secondary batteries. Furthermore, acetylene black and gra By optimizing the mixing ratio of the fen, rapid charging of mobile devices is also possible.

[0219] Note that in Figure 12(B), the active material is 561, graphene is 554, and acetylene black is 5 Areas not filled in 53 indicate voids or binder. Voids are areas where electrolyte seeps in. It is necessary, but too much will reduce the electrode density, and too little will prevent the electrolyte from soaking in. If air gaps remain after the battery is converted into a new battery, the energy density will decrease.

[0220] The positive electrode active material 100 obtained in Embodiment 1 is used as the positive electrode, and acetylene black and G By optimizing the mixing ratio of rhaffen, it is possible to increase the density of the electrodes and create the appropriate gaps necessary for ion conduction. This makes it possible to create a balance between the two, resulting in a secondary system with high energy density and good output characteristics. You can obtain a battery.

[0221] Figure 12(C) shows an example of a cathode using carbon nanotube 555 instead of graphene. This is illustrated. Figure 12(C) shows a different example from Figure 12(B). Carbon nanochips Using Tube 555 prevents the aggregation of carbon black such as acetylene black 553. This can increase diversification.

[0222] Note that in Figure 12(C), the active material 561, carbon nanotube 555, and acetylene are shown. Areas not filled with Black 553 indicate voids or binders.

[0223] Figure 12(D) also illustrates another example of a positive electrode. In Figure 12(C), a graph This example shows the use of carbon nanotube 555 in addition to graphene 554. Using both 4 and carbon nanotube 555, such as acetylene black 553 This prevents carbon black from agglomerating and improves its dispersibility.

[0224] Note that in Figure 12(D), the active material 561, carbon nanotube 555, and graphene are shown. Areas not filled with 554, Acetylene Black 553, refer to voids or binder. It is.

[0225] Using one of the positive electrodes shown in Figures 12(A) to 12(D), place a separator on top of the positive electrode. The laminate, in which the negative electrode is stacked on top of the separator, is placed in a container (such as an outer casing or metal can), A secondary battery can be manufactured by filling a container with an electrolyte solution.

[0226] Furthermore, the above configuration is an example of a secondary battery using an electrolyte, but it is not particularly limited.

[0227] For example, a semi-solid-state battery or an all-solid-state battery can be fabricated using the positive electrode active material 100 shown in Embodiment 1. It is also possible.

[0228] In this specification, a semi-solid battery means that at least one of the electrolyte layer, positive electrode, and negative electrode contains a semi-solid material. This refers to a battery containing a material. Here, "semi-solid" means that the ratio of solid material is 50%. No. A semi-solid is a material that possesses the properties of a solid, such as having little volume change, but also has flexibility. This means that it also possesses some properties similar to those of a liquid. If these properties are satisfied, then It may be one material or multiple materials. For example, a liquid material can be used with a porous solid material. It may also be an infiltrated material.

[0229] In addition, in this specification and the like, a polymer electrolyte secondary battery refers to a battery in which the electrolyte layer between a positive electrode and a negative electrode contains a poly mer. Polymer electrolyte secondary batteries include dry (or intrinsic) poly mer electrolyte batteries and polymer gel electrolyte batteries. A polymer electrolyte secondary battery may also be referred to as a semi-solid battery. A polymer electrolyte secondary battery may also be referred to as a semi-solid battery.

[0230] When a semi-solid battery is fabricated using the positive electrode active material 100 described in Embodiment 1, the semi-solid battery becomes a secondary battery with a large charge-discharge capacity. In addition, a semi-solid battery with high charge-discharge voltage can be obtained. Alternatively, a semi-solid battery with high safety or high reliability can be realized.

[0231] Further, the positive electrode active material described in Embodiment 1 may be used in a mixture with another positive electrode active material.

[0232] Examples of the other positive electrode active material include composite oxides having an olivine-type crystal structure, a layered rock-salt-type crystal structure, or a spinel-type crystal structure. Examples thereof include compounds such as LiFePO₄, LiFe O₂, LiNiO₂, LiMn₂O₄, V₂O₅, Cr₂O₅, and MnO₂. and the like.

[0233] Further, as another positive electrode active material, a lithium-containing material having a spinel-type crystal structure containing manganese, such as LiMn₂O₄ is preferably mixed with lithium nickelate (LiNiO₂ or LiNi 1-x M x O ₂ (0<x<1, M=Co, Al, etc.)). With this structure, the characteristics of the secondary battery can be improved. the characteristics of the secondary battery can be improved.

[0234] Further, as another positive electrode active material, a composition formula Li aMn b M c O d A lithium that can be represented by manganese composite oxide can be used. Here, element M is other than lithium and manganese is preferably a metal element selected from, or silicon, phosphorus, and more preferably nickel is even more preferable. When measuring the entire particles of the lithium manganese composite oxide, during discharge, 0 < a / (b+c) < 2, c > 0, and 0.26 ≦ (b+c) / d < 0.5 is preferably satisfied. Note that the composition of metals, silicon, phosphorus, etc. in the entire particles of the lithium manganese composite oxide can be measured using, for example, ICP-MS (inductively coupled plasma mass spectrometer) can be performed. The composition of oxygen in the entire particles of the lithium manganese composite oxide can be determined by, for example, EDX (energy dispersive X-ray analysis) can be used for measurement. In addition, IC in combination with PMS analysis, valence evaluation by fusion gas analysis and XAFS (X-ray absorption fine structure) analysis can be obtained by using. Note that the lithium manganese composite oxide refers to an oxide containing at least lithium and manganese, and may contain chromium, cobalt, aluminum, nickel , iron, magnesium, molybdenum, zinc, indium, gallium, copper, titanium, niobium, may contain at least one element selected from the group consisting of silicon, phosphorus, and the like .

[0235] <Binder> Examples of the binder include styrene-butadiene rubber (SBR), styrene-isoprene -styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-pro rubber materials such as pylene-diene copolymers are preferably used. As the binder, , fluororubber can be used.

[0236] Furthermore, it is preferable to use a water-soluble polymer as the binder. For example, polysaccharides can be used as the derivative. Cellulose (CMC), methylcellulose, ethylcellulose, hydroxypropylcellulose Cellulose derivatives such as lurose, diacetylcellulose, and regenerated cellulose, as well as starch, etc. These can be used. Furthermore, these water-soluble polymers can be used in combination with the aforementioned rubber materials. It would be even better if they were there.

[0237] Alternatively, as a binder, polystyrene, polymethyl acrylate, polymethyl methacrylate can be used. Chill (polymethyl methacrylate, PMMA), sodium polyacrylate, polyvinyl Alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, Liimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene Polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, It is preferable to use materials such as polyvinyl acetate or nitrocellulose.

[0238] You may use a combination of several of the binders mentioned above.

[0239] For example, a material with particularly excellent viscosity-modifying properties may be used in combination with other materials. For example, rubber materials have excellent adhesive and elastic properties, but when mixed with a solvent, it is difficult to adjust their viscosity. In such cases, for example, mixing with a material that has particularly excellent viscosity-modifying effects may be necessary. This is preferable. As a material with particularly excellent viscosity adjustment effect, for example, a water-soluble polymer can be used. Good. Also, as water-soluble polymers that are particularly excellent in viscosity adjustment, the aforementioned polysaccharides, for example, Boxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydrox Cellulose inducers such as cypropylcellulose, diacetylcellulose, and regenerated cellulose Conductors and starch can be used.

[0240] Furthermore, cellulose derivatives such as carboxymethylcellulose are, for example, carboxymethyl By using salts such as sodium salts or ammonium salts of cellulose, the solubility increases. It becomes easier to exert its effect as a viscosity modifier. The increased solubility makes the electrode slurry - When manufacturing, it is also possible to improve the dispersibility with the active material and other components. As for cellulose and cellulose derivatives used as electrode binders, This also includes salt.

[0241] Water-soluble polymers stabilize viscosity by dissolving in water, and also function as active materials and binders. Other materials to be combined with it, such as styrene-butadiene rubber, are stably separated in an aqueous solution. It can be dispersed. Furthermore, because it has functional groups, it is easily and stably adsorbed onto the surface of the active material. This is expected. Also, cellulose derivatives such as carboxymethylcellulose, For example, many materials have functional groups such as hydroxyl groups and carboxyl groups, and because they have functional groups It is expected that the polymers will interact with each other and exist to broadly cover the surface of the active material.

[0242] When a binder covering or in contact with the surface of the active material forms a film, it is considered a passivation film. It is also expected to play a role in suppressing the decomposition of the electrolyte. Here, the passive film is an electrolytic film. A film that does not conduct air, or a film with extremely low electrical conductivity, for example, on the surface of an active material When a dynamic film is formed, the decomposition of the electrolyte can be suppressed at the battery reaction potential. It can. Furthermore, the passivation film suppresses electrical conductivity, while lithium ions can conduct electricity. And even better.

[0243] <Positive electrode current collector> Current collectors include metals such as stainless steel, gold, platinum, aluminum, and titanium, and these Highly conductive materials such as alloys can be used. Also, the material used for the positive electrode current collector is: It is preferable that the material does not dissolve at the positive electrode potential. Also, silicon, titanium, neodymium, and Scandinavian are preferable. Aluminum alloys to which elements that improve heat resistance, such as um and molybdenum, are added are used. It can also be formed with a metallic element that reacts with silicon to form a silicide. Examples of metallic elements that react with silicon to form silicides include zirconium and titanium. Hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, corn Examples include Baltic and nickel. Current collectors come in foil, plate, sheet, mesh, and perforated metal forms. Shapes such as expanded metal or other shapes can be used as appropriate. The current collector has a thickness of 5 μm. It is best to use materials with a size of 30 μm or less.

[0244] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer also has a negative electrode active material. Furthermore, it may also have a conductive additive and a binder.

[0245] <Negative electrode active material> For example, alloy materials or carbon-based materials can be used as the negative electrode active material.

[0246] As a negative electrode active material, it is possible to perform charge and discharge reactions through alloying and dealloying reactions with lithium. Any suitable element can be used. For example, silicon, tin, gallium, aluminum, galvanic acid. Among the following, a small amount is found in luminum, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one element can be used. Such elements have a larger capacity compared to carbon. In particular, silicon has a high theoretical capacity of 4200 mAh / g. Therefore, silicon is used as the negative electrode active material. It is preferable to use lycon. Alternatively, compounds containing these elements may be used. Example For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V 2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3 Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, I Examples include nSb and SbSn. Here, the charge-discharge reaction occurs through alloying and dealloying reactions with lithium. Elements capable of performing this action, and compounds containing such elements, are sometimes referred to as alloying materials. ru.

[0247] In this specification, SiO refers to silicon monoxide, for example. Alternatively, SiO refers to SiO x It can also be expressed as follows. Here, it is preferable that x has a value of 1 or one neighbor. For example x is preferably between 0.2 and 1.5, and more preferably between 0.3 and 1.2.

[0248] Carbon-based materials include graphite, easily graphitizable carbon (soft carbon), and poorly graphitizable carbon (hard carbon). Carbon, carbon nanotubes, graphene, carbon black, etc. can be used. .

[0249] Examples of graphite include synthetic graphite and natural graphite. An example of synthetic graphite is Mesoca. Examples include carbon microbeads (MCMB), coke-based synthetic graphite, and pitch-based synthetic graphite. Here, spheroidal graphite, which has a spherical shape, can be used as artificial graphite. Furthermore, MCMB may have a spherical shape, which is preferable. Also, the surface area of ​​MCMB Reducing the size is relatively easy and sometimes preferable. Examples of natural graphite include, Examples include flaky graphite and spheroidized natural graphite.

[0250] Graphite is formed when lithium ions are inserted into it (during the formation of lithium-graphite intercalation compounds). It exhibits a low potential, similar to lithium metal (0.05V to 0.3V vs. Li / L). i + ). As a result, lithium-ion secondary batteries using graphite exhibit a high operating voltage. Yes, it is possible. Furthermore, graphite has a relatively high volume per unit volume and relatively small volume expansion. It is preferable because it has advantages such as being inexpensive and having higher safety compared to lithium metal.

[0251] Furthermore, titanium dioxide (TiO2) and lithium titanium oxide (Li4T) are used as negative electrode active materials. i5O 12 ), lithium-graphite intercalation compound (Li x C6), Niobium pentoxide (Nb2O5) Oxides such as tungsten oxide (WO2) and molybdenum oxide (MoO2) can be used. can.

[0252] Furthermore, the negative electrode active material has a Li3N-type structure, which is a lithium and transition metal binitride. Li 3-x M x N(M=Co, Ni, Cu) can be used. For example, Li2.6 Co 0.4 The N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm²). 3 ) indicates And it is preferable.

[0253] When a lithium-transition metal binitride is used, lithium ions are included in the negative electrode active material, Combined with lithium-ion-free materials such as V2O5 and Cr3O8 as positive electrode active materials. This is preferable. By pre-desorbing the lithium ions contained in the positive electrode active material, the negative electrode active material is used. A lithium-transition metal composite can be used.

[0254] Furthermore, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example, Lithium oxide, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO). Transition metal oxides that do not form alloys with the negative electrode active material may be used. The resulting materials include Fe2O3, CuO, Cu2O, RuO2, Cr2O3, etc. CoS oxides 0.89 , sulfides such as NiS and CuS, Zn3N2, Cu3N, Ge3 Nitrides such as N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. It can also occur with fluoride.

[0255] The conductive additives and binders that the negative electrode active material layer may have include the positive electrode active material layer Materials similar to conductive additives and binders can be used.

[0256] <Negative electrode current collector> In addition to the same materials as the positive electrode current collector, copper and other materials can also be used for the negative electrode current collector. It is preferable to use a material for the electrode current collector that does not alloy with carrier ions such as lithium.

[0257] [Separator] A separator is placed between the positive and negative electrodes. Examples of separators include paper. Fibers containing cellulose, nonwoven fabrics, glass fibers, ceramics, or nylon (poly Amide, Vinylon (polyvinyl alcohol-based fiber), Polyester, Acrylic, Polyol Materials made from synthetic fibers such as polyurethane can be used. The parator is preferably processed into a bag shape and positioned to enclose either the positive or negative electrode. It seems so.

[0258] The separator may have a multilayer structure. For example, organic materials such as polypropylene and polyethylene. The material film contains ceramic-based materials, fluorine-based materials, polyamide-based materials, or a mixture thereof. A combination of these materials can be used as a coating. Examples of ceramic materials include aluminum oxide. Examples of fluorine-based materials include nium particles, silicon oxide particles, etc. PVDF, polytetrafluoroethylene, etc. can be used as polyamide materials. For example, nylon, aramid (meta-aramid, para-aramid), etc. can be used. can.

[0259] Coating with ceramic materials improves oxidation resistance, thus preventing separation during high-voltage charging and discharging. This can suppress degradation of the battery and improve the reliability of secondary batteries. Furthermore, by using fluorine-based materials... This allows the separator and electrodes to adhere more closely, improving the output characteristics. Coating with polyamide materials, especially aramid, improves heat resistance, thus increasing the safety of secondary batteries. It can improve overall health.

[0260] For example, a mixture of aluminum oxide and aramid material is coated on both sides of a polypropylene film. It may also be done by using aluminum oxide on the surface of the polypropylene film that is in contact with the positive electrode. A mixed material of aramid may be coated, and a fluorine-based material may be coated on the surface in contact with the negative electrode.

[0261] Using a multilayer separator ensures the safety of the secondary battery even if the overall thickness of the separator is thin. Because it can maintain this state, the capacity per unit volume of a secondary battery can be increased.

[0262] [Electrolyte] An electrolyte solution contains a solvent and an electrolyte. A non-protic organic solvent is preferred as the solvent for the electrolyte solution. For example, ethylene carbonate (EC), propylene carbonate (PC), and buty Lenyl carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolane Chtone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate Methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1 ,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfone Hoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetra One of the following: lahydrofuran, sulfolane, sultone, or two or more of these. It can be used in combinations and ratios.

[0263] Furthermore, as the solvent for the electrolyte, an ionic liquid (a room-temperature molten salt) that is flame-retardant and non-volatile is used. By using one or more of these, the internal temperature of the energy storage device will rise due to internal short circuits or overcharging. This can also prevent the rupture or ignition of energy storage devices. Ionic liquids contain cations and anions. It consists of organic cations and anions. As organic cations used in the electrolyte, quaternary cations are used. Ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, etc. aliphatic onium cations, imidazolium cations, pyridinium cations, etc. Aromatic cations are one example. Also, monovalent amide-based anions are used as anions in the electrolyte. Nions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl Sulfonate anions, tetrafluoroborate anions, perfluoroalkyl borates Anions, hexafluorophosphate anions, or perfluoroalkyl phosphates Examples include anions.

[0264] Furthermore, examples of electrolytes to be dissolved in the above solvent include LiPF6, LiClO4, and Li AsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4 Li2B 10 Cl 10 Li2B 12 Cl 12 LiCF3SO3, LiC4F9SO 3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2) 2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, Lithium Lithium salts such as mbiso(oxalate)borate (Li(C2O4)2, LiBOB) One type, or two or more of these types, can be used in any combination and ratio. .

[0265] The electrolyte used in the energy storage device may contain particulate matter and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as "non-contaminated"). It is preferable to use a highly purified electrolyte with a low content of (also called "pure substance"). Specifically, the weight ratio of impurities to the electrolyte should be 1% or less, preferably 0.1% or less, more preferably It is preferable that the amount be 0.01% or less.

[0266] Furthermore, the electrolyte contains vinylene carbonate, propanesultone (PS), and tert-butylbe. TBB (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate) LiBOB (Lithium-Borate), as well as dinitriles such as succinonitrile and adiponitrile. Additives such as compounds may be added. The concentration of the additive should be, for example, 0.1% of the total solvent. It should be between wt% and 5wt%.

[0267] Alternatively, a polymer gel electrolyte, obtained by swelling a polymer with an electrolyte solution, may be used.

[0268] Using polymer gel electrolytes enhances safety against leakage and other issues. Furthermore, secondary batteries... It is possible to make it thinner and lighter.

[0269] Examples of polymers that can be gelled include silicone gel, acrylic gel, and acrylonitrile gel. Polyethylene oxide gels, polypropylene oxide gels, fluorine polymers Gels and the like can be used. For example, polyalkyl substances such as polyethylene oxide (PEO) Polymers having a ylene oxide structure, PVDF, polyacrylonitrile, and so on. Copolymers containing these can be used. For example, PVDF and hexafluoropropylene PVDF-HFP, a copolymer of pyrene (HFP), can be used. The polymer being processed may have a porous structure.

[0270] In addition, instead of an electrolyte, a solid electrolyte containing inorganic materials such as sulfide-based or oxide-based materials, or P Solid electrolytes containing polymer materials such as EO (polyethylene oxide) can be used. When using a solid electrolyte, the installation of separators and spacers becomes unnecessary. Because the entire pond can be solidified, the risk of leakage is eliminated, dramatically improving safety.

[0271] Therefore, the positive electrode active material 100 obtained in Embodiment 1 can also be applied to all-solid-state batteries. By applying the positive electrode slurry or electrode to an all-solid-state battery, high safety and characteristics can be achieved. A good all-solid-state battery can be obtained.

[0272] [Exterior] For the casing of a secondary battery, metal materials such as aluminum or resin materials are used. It is possible to have it. Also, a film-like outer covering can be used. For example, polyethylene, polypropylene, polycarbonate, ionomer, polyamide On a film made of materials such as aluminum, stainless steel, copper, nickel, etc., which have excellent flexibility A thin metal film is provided, and on the thin metal film, a polyamide resin, polyester resin, etc. are used as the outer surface of the exterior body. A three-layer film with an insulating synthetic resin film, such as a tellate resin, can be used.

[0273] This embodiment can be used in combination with other embodiments.

[0274] (Embodiment 4) In this embodiment, the positive or negative electrode is manufactured by the manufacturing method described in the previous embodiment. This section describes examples of various shapes of secondary batteries that have electrodes.

[0275] [Coin-type rechargeable battery] An example of a coin-type rechargeable battery will be described. Figure 13(A) shows a coin-type (single-layer flattened) battery. Figure 13(B) is an external view of a secondary battery, and Figure 13(C) is a cross-section view of the battery. This is a view drawing. Coin-type rechargeable batteries are mainly used in small electronic devices.

[0276] In Figure 13(A), the overlapping of the components (up / down relationship and positional relationship) is shown for clarity. A schematic diagram is provided for clarity. Therefore, Figure 13(A) and Figure 13(B) are perfectly identical pairs. It is not intended as a diagram.

[0277] In Figure 13(A), the positive electrode 304, separator 310, negative electrode 307, spacer 322, and washer Two Shear 312s are stacked. These are sealed with a negative electrode can 302 and a positive electrode can 301. In Figure 16(A), the gasket for sealing is not shown. Spacer 322, Washer 312 protects the inside or can when crimping the positive electrode can 301 and the negative electrode can 302. It is used to fix the internal position. Spacer 322 and washer 312 are stainless steel. Use a resin or insulating material.

[0278] The positive electrode 304 is a laminated structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305. .

[0279] To prevent a short circuit between the positive and negative electrodes, a separator 310 and a ring-shaped insulator 313 are connected to the positive electrode 304. They are positioned to cover the sides and top surfaces, respectively. The separator 310 is positioned more than the positive electrode 304. It has a large surface area.

[0280] Figure 13(B) is a perspective view of the completed coin-type rechargeable battery.

[0281] The coin-type rechargeable battery 300 consists of a positive electrode casing 301, which also serves as the positive terminal, and a negative electrode casing, which also serves as the negative terminal. 302 is insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 consists of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with it. It is formed by the following. The negative electrode 307 is provided in contact with the negative electrode current collector 308. It is formed by a negative electrode active material layer 309. Furthermore, the negative electrode 307 is limited to a laminated structure. Alternatively, lithium metal foil or a lithium-aluminum alloy foil may be used.

[0282] Furthermore, the positive electrode 304 and negative electrode 307 used in the coin-type secondary battery 300 are each made of live metal The layers only need to be formed on one side.

[0283] The positive electrode container 301 and the negative electrode container 302 are made of nickel and aluminum, which are corrosion-resistant to the electrolyte. , metals such as titanium, or alloys thereof, or alloys of these with other metals (e.g., stainless steel) (etc.) can be used. In addition, nickel and aluminum can be used to prevent corrosion by electrolytes, etc. It is preferable to coat with nium or the like. The positive electrode can 301 is the positive electrode 304, and the negative electrode can 302 is the negative electrode Connect each of the 307s electrically.

[0284] These negative electrode 307, positive electrode 304, and separator 310 are immersed in the electrolyte, as shown in Figure 13(C). As shown, with the positive electrode can 301 at the bottom, the positive electrode 304, separator 310, negative electrode 307, and negative electrode... The cans 302 are stacked in this order, and the positive electrode can 301 and the negative electrode can 302 are connected via the gasket 303. The coin-shaped rechargeable battery 300 is manufactured by crimping the parts together.

[0285] By using a rechargeable battery, it achieves high capacity, high charge / discharge capacity, and excellent cycle characteristics. This can be a coin-type rechargeable battery 300. Note that there are two between the negative electrode 307 and the positive electrode 304. When used as a secondary battery, the separator 310 can be omitted.

[0286] [Cylindrical rechargeable battery] An example of a cylindrical secondary battery will be explained with reference to Figure 14(A). Cylindrical secondary battery 61 As shown in Figure 14(A), 6 has a positive electrode cap (battery cover) 601 on its top surface, and its sides and The battery can (outer casing) 602 is located on the bottom. These positive electrode cap 601 and battery can (outer casing) The container (602) is insulated by the gasket (insulating packing) 610.

[0287] Figure 14(B) is a schematic diagram showing a cross-section of a cylindrical secondary battery. The cylindrical rechargeable battery has a positive electrode cap (battery cover) 601 on the top surface, and on the sides and bottom It has a battery can (outer can) 602. These positive electrode cap and battery can (outer can) 602 and It is insulated by a gasket (insulating packing) 610.

[0288] Inside the hollow cylindrical battery can 602, there is a strip-shaped positive electrode 604 and a negative electrode 606 separated by a separator 6 A battery element is provided wound with 05 in between. Although not shown in the diagram, the battery element is center It is wound around the shaft. Battery casing 602 is closed at one end and open at the other. Can 602 contains metals such as nickel, aluminum, and titanium that are corrosion-resistant to the electrolyte. or use alloys of these metals or alloys of these metals with other metals (e.g., stainless steel). This can be done. Also, to prevent corrosion by the electrolyte, nickel and aluminum are used in the battery can. It is preferable to cover 02. Inside the battery can 602, the positive electrode, negative electrode and separator The battery element, around which the data is wound, is sandwiched between a pair of opposing insulating plates 608 and 609. Furthermore, the inside of the battery can 602, in which the battery elements are installed, is filled with a non-aqueous electrolyte (not shown). The non-aqueous electrolyte can be the same as that used in coin-type rechargeable batteries.

[0289] Since the positive and negative electrodes used in cylindrical storage batteries are wound, active material is formed on both sides of the current collector. It is preferable to do so.

[0290] By using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode 604, high capacity and, This allows for the creation of a cylindrical secondary battery 616 with high charge / discharge capacity and excellent cycle characteristics. Cut.

[0291] The positive electrode 604 is connected to the positive electrode terminal (positive electrode current collector lead) 603, and the negative electrode 606 is connected to the negative electrode terminal The (negative current collector lead) 607 is connected. Both the positive terminal 603 and the negative terminal 607 are Metal materials such as aluminum can be used. The positive terminal 603 is connected to the safety valve mechanism 61 3. The negative terminals 607 are resistance-welded to the bottom of the battery can 602. Safety valve mechanism 613 This is a PTC element (Positive Temperature Coefficient It is electrically connected to the positive electrode cap 601 via 611. The safety valve mechanism 613 is electrically connected to the positive electrode cap 601. When the internal pressure of the pond rises above a predetermined threshold, the electrical current between the positive electrode cap 601 and the positive electrode 604 This disconnects the connection. Also, the PTC element 611 has resistance when the temperature rises. It is a thermal resistance element that increases resistance, and by limiting the amount of current due to the increase in resistance, it prevents abnormal heat generation. Therefore, PTC elements use barium titanate (BaTiO3)-based semiconductor ceramics, etc. You can use it.

[0292] Figure 14(C) shows an example of the energy storage system 615. The energy storage system 615 consists of multiple secondary batteries. It has 616. The positive electrode of each secondary battery is a conductor 624 separated by an insulator 625. It is in contact with and electrically connected to the control circuit 624 via the wiring 623. It is electrically connected to 0. Also, the negative terminal of each secondary battery is connected via wiring 626. It is electrically connected to the control circuit 620. The control circuit 620 is responsible for charging and discharging. Discharge control circuits and protection circuits to prevent overcharging or over-discharging can be applied.

[0293] Figure 14(D) shows an example of the energy storage system 615. The energy storage system 615 has multiple secondary power It has a battery 616, and multiple secondary batteries 616 are sandwiched between conductive plates 628 and 614. Multiple secondary batteries 616 are connected to conductive plates 628 and 614 by wiring 627. They are connected electrically. Multiple secondary batteries 616 may be connected in parallel or in series. They may be connected in parallel and then further connected in series. By configuring a power storage system 615 having a battery 616, it is possible to extract a large amount of power. can.

[0294] Multiple secondary batteries 616 may be connected in parallel and then further connected in series.

[0295] A temperature control device may be provided between multiple secondary batteries 616. If the secondary batteries 616 overheat... When this happens, the temperature control device cools the battery, and if the secondary battery 616 gets too cold, the temperature control device... The device can be heated. Therefore, the performance of the energy storage system 615 is affected by the outside temperature. It becomes less likely to happen.

[0296] Furthermore, in Figure 14(D), the energy storage system 615 has wiring 621 and distribution to the control circuit 620. They are electrically connected via wire 622. Wiring 621 is connected via conductive plate 628 to multiple twins The wiring 622 is connected to the positive terminal of the secondary battery 616, and the wiring 622 is connected to the negative terminal of the multiple secondary batteries 616 via the conductive plate 614. They are electrically connected to each other.

[0297] [Other structural examples of secondary batteries] Examples of secondary battery structures will be explained using Figures 15 and 16.

[0298] The secondary battery 913 shown in Figure 15(A) has terminals 951 and 952 inside the housing 930. It has a wound body 950. The wound body 950 is immersed in an electrolyte inside the housing 930. Terminal 952 is in contact with the housing 930, and terminal 951 is in contact with the housing by using insulating material, etc. It is not in contact with the body 930. Note that in Figure 15(A), for convenience, the housing 930 is separated. As shown in the diagram, in reality the wound body 950 is covered by the housing 930, and terminals 951 and 95 2 extends outside the casing 930. The casing 930 is made of a metal material (e.g., aluminum). Materials such as lum or resin can be used.

[0299] Furthermore, as shown in Figure 15(B), the housing 930 shown in Figure 15(A) is made of multiple materials. They may be formed. For example, the secondary battery 913 shown in Figure 15(B) has a housing 930a and a housing 9 30b is bonded together, and the area enclosed by the housing 930a and housing 930b is wound up 9 50 is provided.

[0300] For the casing 930a, insulating materials such as organic resin can be used. In particular, the antenna By using a material such as organic resin on the surface where the electric field of the secondary battery 913 is formed, Shielding can be suppressed. Furthermore, if the shielding of the electric field by the housing 930a is small, the housing 930a An antenna may be installed inside. For the housing 930b, for example, a metal material may be used. can.

[0301] Furthermore, the structure of the wound body 950 is shown in Figure 15(C). The wound body 950 is the negative electrode 931 The coiled body 950 has a positive electrode 932 and a separator 933. The negative electrode 931 and the positive electrode 932 are stacked on top of each other with a sash in between, and the stacked sheet is rolled up. It is a wound body. Furthermore, the negative electrode 931, the positive electrode 932, and the separator 933 are stacked together. You can also stack multiple of them.

[0302] Alternatively, the secondary battery 913 may have a wound body 950a as shown in Figure 16. Figure 16 The wound body 950a shown in (A) has a negative electrode 931, a positive electrode 932, and a separator 933. Possibly has. The negative electrode 931 has a negative electrode active material layer 931a. The positive electrode 932 has a positive electrode active material layer 932 It has a.

[0303] By using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode 932, high capacity and, This allows for a secondary battery 913 with high charge / discharge capacity and excellent cycle characteristics.

[0304] The separator 933 has a wider width than the negative electrode active material layer 931a and the positive electrode active material layer 932a. It is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. Furthermore, the fact that the negative electrode active material layer 931a is wider than the positive electrode active material layer 932a is a safety consideration. This is preferable. Furthermore, a wound body 950a of this shape is preferable because it offers good safety and productivity. .

[0305] As shown in Figure 16(B), the negative electrode 931 is ultrasonically bonded, welded, or crimped to the terminal 951. They are electrically connected. Terminal 951 is electrically connected to terminal 911a. Also, the positive terminal Terminal 932 is electrically connected to terminal 952 by ultrasonic bonding, welding, or crimping. Terminal 952 is electrically connected to terminal 911b.

[0306] As shown in Figure 16(C), the coiled body 950a and the electrolyte are covered by the housing 930, The next battery is 913. It is preferable to provide a safety valve, overcurrent protection element, etc., in the housing 930. The safety valve is a valve that opens when the inside of the housing 930 reaches a predetermined internal pressure in order to prevent the battery from rupturing. ru.

[0307] As shown in Figure 16(B), the secondary battery 913 may have multiple wound bodies 950a. By using multiple windings 950a, a secondary battery 913 with a larger charge / discharge capacity can be created. This is possible. Other elements of the secondary battery 913 shown in Figures 16(A) and (B) are shown in Figure 15(A). The description of the secondary battery 913 shown in (C) through (F) can be taken into consideration.

[0308] <Laminated rechargeable battery> Next, regarding an example of a laminated secondary battery, an example of an external view is shown in Figures 17(A) and 17( Figure B) shows the positive electrode 503, negative electrode 506, and separator 5 07, it has an outer casing 509, a positive lead electrode 510, and a negative lead electrode 511.

[0309] Figure 18(A) shows the external view of the positive electrode 503 and the negative electrode 506. The positive electrode 503 is the positive electrode current collector 50 The positive electrode has a positive electrode active material layer 502 formed on the surface of the positive electrode current collector 501. 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as the tab region). Negative electrode 506 has a negative electrode current collector 504, and the negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. Furthermore, the negative electrode 506 is the region where the negative electrode current collector 504 is partially exposed, i.e., the tab region. It has a tab region. The area and shape of the tab regions of the positive and negative electrodes are not limited to the example shown in Figure 18(A). I can't.

[0310] <Method 1 for manufacturing laminated rechargeable batteries> Here, we will describe an example of a method for manufacturing a laminate-type secondary battery, as shown in Figure 17(A) in its external view. This will be explained using Figures 18(B) and 18(C).

[0311] First, the negative electrode 506, separator 507, and positive electrode 503 are stacked. (See Figure 18(B) for details.) The negative electrode 506, separator 507, and positive electrode 503 are shown. Here, there are 5 sets of negative electrodes and 5 sets of positive electrodes. An example using four sets is shown. It can also be called a laminate consisting of a negative electrode, a separator, and a positive electrode. Next, the positive electrode The tab regions of 503 are joined together, and the positive lead electrode 510 is made contact with the tab region of the outermost positive electrode. Perform the joining. For joining, ultrasonic welding, for example, may be used. Similarly, the tab region of the negative electrode 506 The regions are joined together, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0312] Next, the negative electrode 506, separator 507, and positive electrode 503 are placed on the outer casing 509.

[0313] Next, as shown in Figure 18(C), the outer casing 509 is folded at the part indicated by the dashed line. Next, the outer perimeter of the exterior body 509 is joined. For joining, for example, heat compression bonding may be used. In order to allow the electrolyte 508 to be added later, a part (or one side) of the outer casing 509 A region that is not connected (hereinafter referred to as the inlet) is provided.

[0314] Next, the electrolyte 508 (not shown) is introduced into the outer casing 509 through the inlet provided in the outer casing 5 Introduce into the inside of 09. Introduce electrolyte 508 under reduced pressure or inert atmosphere. It is preferable to do so. And finally, the inlet is joined. In this way, Figure 17(A) Furthermore, a laminate-type secondary battery 600 can be manufactured as shown in Figure 17(B).

[0315] By using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode 503, high capacity and, This allows for the creation of a secondary battery 600 with high charge / discharge capacity and excellent cycle characteristics.

[0316] <Method for manufacturing laminated rechargeable batteries, part 2> Next, regarding an example of the manufacturing method for the laminate-type secondary battery 600 shown in Figure 17(C), 19. Using Figures 20, 21(A) to 21(D), and 22(A) to 22(F) Let me explain. The secondary battery 600 shown in Figure 17(C) has a positive electrode 503, a negative electrode 506, and a separate It has a lead electrode 507, an outer casing 509, a positive lead electrode 510, and a negative lead electrode 511. The outer casing 509 is sealed by a seal 516.

[0317] The laminated secondary battery 600 can be manufactured, for example, using the manufacturing apparatus shown in Figure 19. This can be done. The manufacturing apparatus 800 shown in Figure 19 includes a material input chamber 801, a transport chamber 802, and a processing chamber 8 It has 03 and a component removal chamber 806. Each chamber has various exhaust mechanisms depending on its intended use. A configuration that connects to the above can be applied. In addition, each room can be equipped with various gas supply mechanisms depending on its intended use. The connected configuration can be applied to prevent impurities from entering the manufacturing apparatus 800. It is preferable that an inert gas is supplied to the manufacturing apparatus 800. The gas supplied to the interior of 0 is purified by a gas purifier before being introduced into the manufacturing equipment 800. It is preferable to use a regulated version. The component input chamber 801 contains the positive electrode, separator, and negative electrode. This is a room for loading the outer casing and other components into the manufacturing apparatus 800. The transport room 802 is a transport mechanism It has 820. The processing chamber 803 has a stage and an electrolyte dropping mechanism.

[0318] The procedure for manufacturing the laminate-type secondary battery 600 is as follows. The component removal chamber 806 is This is a room for removing the manufactured secondary batteries from the manufacturing equipment 800.

[0319] First, the outer casing 509b is placed on the stage 831 of the processing chamber 803, and then the outer casing 50 The positive electrode 503 is placed on 9b (Figures 21(A) and 21(B)). Next, nozzle 83 Electrolyte 525a is dropped onto the positive electrode 503 from 4 (Figures 21(C) and 21(D)). Figure 21(D) is a cross-section corresponding to the dashed line AB in Figure 21(C). Note that the drawing is complicated. To avoid sloppiness, the description of Stage 831 may be omitted. The method of application is, for example... If so, use one of the following methods: dispensing method, spray method, or inkjet method. This is possible. Furthermore, the ODF (One Drop Fill) method is used for electrolyte dispensing. It is possible.

[0320] By moving the nozzle 834, the electrolyte 525a is dropped onto the entire surface of the positive electrode 503. This can be done by moving the stage 831 across the entire surface of the positive electrode 503. Alternatively, electrolyte 525a can be added dropwise.

[0321] The electrolyte should be dropped from a position where the shortest distance from the surface to be dropped is greater than 0 mm and less than or equal to 1 mm. It is preferable that this be done.

[0322] Furthermore, it is preferable to adjust the viscosity of the electrolyte dripped from the nozzle or the like as appropriate. The viscosity at room temperature (25°C) is in the range of 0.3 mPa·s to 1000 mPa·s. If it's inside, it can be dispensed by dripping from the nozzle.

[0323] Furthermore, since the viscosity of an electrolyte changes with its temperature, the temperature of the electrolyte being added must also be appropriate. It is preferable to adjust the temperature as appropriate. The temperature of the electrolyte should be above its melting point and below its boiling point, and A temperature below the ignition point is preferable.

[0324] Next, the separator 507 is placed on the positive electrode 503 so as to overlap the entire surface of the positive electrode 503. (Figure 22(A)). Next, using the nozzle 834, the electrolyte 52 is placed on the separator 507. Add 5b dropwise (Figure 22(B)). Then, place the negative electrode 506 on the separator 507. (Figure 22(C)). The negative electrode 506 does not protrude from the separator 507 when viewed from above. They are arranged in an overlapping manner. Next, the electrolyte 525 is placed on the negative electrode 506 using the nozzle 834. c is added dropwise (Figure 22(D)). Then, the positive electrode 503, separator 507, and negative electrode 5 By further stacking the 06 laminate, the laminate 512 shown in Figure 20 can be fabricated. Yes, it is possible. Next, the outer casings 509a and 509b connect the positive electrode 503 and the separator 5 07 and the negative electrode 506 are sealed (Figures 22(E) and 22(F)).

[0325] By arranging multiple laminates 512 on the outer casing 509b, multi-faceted processing can be performed. Each laminate 512 is sealed in the seal region surrounding the laminate 512, and then the seal region By separating it on the outside, multiple secondary batteries can be individually isolated.

[0326] During sealing, first, a frame-shaped resin layer is formed on the outer casing 509b. Next, under reduced pressure, the resin layer By irradiating at least a portion of it with light, at least a portion of the resin layer is cured. Next, The sealing is performed under atmospheric pressure. Alternatively, after the above light irradiation, the sealing is performed by thermocompression or welding. Alternatively, sealing by heat compression or welding alone may be performed without the light irradiation sealing described above. That's fine.

[0327] Figure 17(C) shows an example where the outer casing 509 is sealed on all four sides, but Figure 17(A) also shows an example where the outer casing 509 is sealed on all four sides. The seal may be sealed in three directions, as shown in Figure 17(B).

[0328] [Example of a battery pack] Figure 2 shows an example of a secondary battery pack according to one embodiment of the present invention that can be wirelessly charged using an antenna. I will explain using number 3.

[0329] Figure 23(A) shows the external appearance of the secondary battery pack 531, which has a thin rectangular parallelepiped shape. It can also be described as a thick, flat plate shape. Figure 23(B) shows the configuration of the secondary battery pack 531. This is an explanatory diagram. The secondary battery pack 531 consists of the circuit board 540 and the secondary battery 513. It has. A label 529 is attached to the secondary battery 513. The circuit board 540 has a seal. It is fixed by 515. The secondary battery pack 531 also has an antenna 517. .

[0330] The interior of the secondary battery 513 may have a structure with a wound body or a structure with a laminated body. That's fine.

[0331] In the secondary battery pack 531, for example, as shown in Figure 23(B), on the circuit board 540 It has a control circuit 590. The circuit board 540 is electrically connected to terminal 514. It is there. Also, the circuit board 540 has the antenna 517, the positive lead and negative lead of the secondary battery 513. One end of the lead, 551, is electrically connected to the other end of the positive and negative leads, 552.

[0332] Alternatively, as shown in Figure 23(C), a circuit system 59 is provided on the circuit board 540. 0a and circuit system 590b which is electrically connected to circuit board 540 via terminal 514. It may have the following:

[0333] Furthermore, the antenna 517 is not limited to a coil shape; for example, it may be linear or plate-shaped. Planar antenna, aperture antenna, traveling wave antenna, EH antenna, magnetic field antenna, dielectric An antenna such as a body antenna may be used. Alternatively, antenna 517 may be a flat conductor. This flat conductor can function as one of the conductors for electric field coupling. Antenna 517 functions as one of the two conductors of the capacitor. This is also possible. This allows for the exchange of power not only through electromagnetic and magnetic fields, but also through electric fields. Cut.

[0334] The secondary battery pack 531 has a layer 519 between the antenna 517 and the secondary battery 513. The layer 519 has the function of shielding electromagnetic fields, for example, from the secondary battery 513. For layer 519, for example, a magnetic material can be used.

[0335] This embodiment can be freely combined with other embodiments.

[0336] (Embodiment 5) In this embodiment, an all-solid-state battery is fabricated using the positive electrode active material 100 obtained in Embodiment 1. Here is an example.

[0337] As shown in Figure 24(A), a secondary battery 400 according to one aspect of the present invention comprises a positive electrode 410 and a solid electrolytic cell. It has a solid layer 420 and a negative electrode 430.

[0338] The positive electrode 410 has a positive electrode current collector 413 and a positive electrode active material layer 414. The device has a positive electrode active material 411 and a solid electrolyte 421. The positive electrode active material 411 has an embodiment The positive electrode active material 100 obtained in state 1 is used. The positive electrode active material layer 414 is a conductive additive. It may have a binder.

[0339] The solid electrolyte layer 420 has a solid electrolyte 421. The solid electrolyte layer 420 has a positive electrode 410 and It is located between the negative electrodes 430 and does not have either the positive electrode active material 411 or the negative electrode active material 431. It is a domain.

[0340] The negative electrode 430 has a negative electrode current collector 433 and a negative electrode active material layer 434. It has a negative electrode active material 431 and a solid electrolyte 421. The negative electrode active material layer 434 is conductive It may contain auxiliary agents and binders. Note that when metallic lithium is used for the negative electrode 430. As shown in Figure 24(B), the negative electrode 430 can be made without a solid electrolyte 421. Using metallic lithium in the negative electrode 430 improves the energy density of the secondary battery 400. It is preferable to be able to do so.

[0341] The solid electrolyte 421 in the solid electrolyte layer 420 may be, for example, a sulfide-based solid electrolyte or an acid Compound-based solid electrolytes, halogenated solid electrolytes, etc., can be used.

[0342] Sulfide-based solid electrolytes include thiosilicon-based (Li 10 GeP2S 12 Li 3.25 Ge 0.25 P 0.75 S4, etc.), sulfide glass (70Li2S・30P2S5, 30Li2 S·26B2S3·44LiI, 63Li2S·38SiS2·1Li3PO4, 57L i2S・38SiS2・5Li4SiO4, 50Li2S・50GeS2, etc.), sulfide crystals Crystallized glass (Li7P3S 11 Li 3.25 P 0.95 Contains S4, etc. Sulfide-based Solid electrolytes include materials with high conductivity, can be synthesized at low temperatures, and are relatively soft. It has advantages such as the conductivity path being easily maintained even after repeated charging and discharging.

[0343] Oxide-based solid electrolytes include materials having a perovskite-type crystal structure (La 2 / 3-x Li 3x Materials having a NASICON-type crystal structure (Li 1-Y Al Y Ti 2- Y (PO4)3 etc.) Materials having a garnet-type crystal structure (Li7La3Zr2O 12 etc. ), materials having a LISICON-type crystal structure (Li 14 ZnGe4O 16 etc.), LLZO (Li7La3Zr2O 12 ), oxide glass (Li3PO4-Li4SiO4, 50L i4SiO4·50Li3BO3 etc.), oxide crystallized glass (Li 1.07 Al 0.69 Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5(PO4)3 etc. is included. Oxide-based solid electrolytes have advantages such as being stable in the atmosphere.

[0344] Halide-based solid electrolytes include LiAlCl4, Li3InBr6, LiF, and LiCl These include LiBr, LiI, etc. Furthermore, these halide-based solid electrolytes are porous Composite materials, such as aluminum oxide or porous silica filled with pores, can also be used as solid electrolytes. It can be used.

[0345] Alternatively, different solid electrolytes may be mixed and used.

[0346] In particular, Li has a NASICON-type crystal structure. 1+x Al x Ti 2-x (PO4)3( 0[x[1] (hereinafter referred to as LATP) is aluminum and titanium, which are two components of one aspect of the present invention. Because it contains elements that may be present in the positive electrode active material used in the next battery 400, it improves cycle characteristics. Therefore, a synergistic effect can be expected, which is desirable. Furthermore, an improvement in productivity can be expected through process reduction. In this specification, the NASICON-type crystal structure is defined as M2(XO4)3(M:transition). A compound represented by a metal transfer (X:S, P, As, Mo, W, etc.), consisting of an MO6 octahedron and XO This refers to a structure in which four tetrahedrons share vertices and are arranged in a three-dimensional manner.

[0347] [Shape of the outer casing and secondary battery] In one aspect of the present invention, the casing of the secondary battery 400 can be made of various materials and shapes. While this is possible, it is preferable that the positive electrode, solid electrolyte layer, and negative electrode have the function of pressurizing them.

[0348] For example, Figure 25 shows an example of a cell used to evaluate the materials of an all-solid-state battery.

[0349] Figure 25(A) is a schematic cross-sectional view of the evaluation cell, which consists of a lower member 761 and an upper member 762 and fixing screws and wing nuts 764 that secure them, and a retaining screw 763 The electrode plate 753 is pressed against the plate by rotating it, securing the evaluation material. (Stainless steel material) An insulator 766 is provided between the lower member 761, which is made of material, and the upper member 762. There is also an O-ring 7 for sealing between the upper member 762 and the retaining screw 763. 65 is provided.

[0350] The evaluation material is placed on an electrode plate 751, surrounded by an insulating tube 752, and subjected to electrical stimulation from above. The material is being pressed by the polarity plate 753. This is a magnified, oblique view of the area around the evaluation material. The figure is shown in Figure 25(B).

[0351] As an example of the evaluation material, we show a stacked structure consisting of a positive electrode 750a, a solid electrolyte layer 750b, and a negative electrode 750c. The cross-sectional view is shown in Figure 25(C). Note that the same part is shown in Figures 25(A) to (C). The same symbol is used for the location.

[0352] The electrode plate 751 and lower member 761, which are electrically connected to the positive electrode 750a, are the positive electrode It can be said that this corresponds to a terminal. It is an electrode plate electrically connected to the negative electrode 750c. 753 and the upper member 762 can be said to correspond to the negative electrode terminal. Electrode plate While applying pressure to the evaluation material via the 751 and electrode plate 753, electrical resistance and other parameters are measured. It can be measured.

[0353] Furthermore, the outer casing of the secondary battery according to one aspect of the present invention uses a package with excellent airtightness. This is preferable. For example, ceramic packages or resin packages can be used. Furthermore, when sealing the outer casing, it is necessary to block out outside air and seal it in a tightly sealed atmosphere, for example, a glove box. It is preferable to perform this within the premises.

[0354] Figure 26(A) shows a secondary battery according to one embodiment of the present invention, having an exterior and shape different from that of Figure 25. A perspective view is shown. The secondary battery in Figure 26(A) has external electrodes 771 and 772 and multiple packs. It is sealed with an outer casing that includes a cage member.

[0355] Figure 26(B) shows an example of a cross-section cut along the dashed line in Figure 26(A). Positive electrode 750a, The laminate having a solid electrolyte layer 750b and a negative electrode 750c has an electrode layer 773a provided on a flat plate. The package member 770a is cut, the frame-shaped package member 770b is cut, and the electrode layer 7 is on the flat plate. The package member 770c, which has 73b provided, is enclosed and sealed by the structure. The package components 770a, 770b, and 770c contain insulating materials, such as resin materials and ceramics. Mick can be used.

[0356] The external electrode 771 is electrically connected to the positive electrode 750a via the electrode layer 773a. It functions as a positive terminal. In addition, the external electrode 772 is electrically negative via the electrode layer 773b. It is electrically connected to the 750c pole and functions as a negative terminal.

[0357] By using the positive electrode active material 100 obtained in Embodiment 1, a high energy density and good performance can be achieved. This makes it possible to realize an all-solid-state secondary battery with output characteristics.

[0358] This embodiment can be used in appropriate combination with other embodiments.

[0359] (Embodiment 6) This embodiment is a different example from Figure 14(D), which is a cylindrical secondary battery. Figure 27( An example of applying C) to electric vehicles (EVs) is shown.

[0360] Electric vehicles have a first battery 1301a, 1301 as the main secondary battery for propulsion. b and a second battery that supplies power to the inverter 1312 which starts the motor 1304. 1311 is installed. The second battery 1311 is the cranking battery (star Also called a ter battery. The second battery 1311 can output high power if Often, high capacity is not required, and the capacity of the second battery 1311 is less than that of the first battery. It is smaller compared to 1301a and 1301b.

[0361] The internal structure of the first battery 1301a is as shown in Figure 15(A) or Figure 16(C) It may be a molded type, or it may be a laminated type as shown in Figure 17(A) or Figure 17(B). Furthermore, the first battery 1301a may be the all-solid-state battery of Embodiment 5. By using the all-solid-state battery of Embodiment 5 in battery 1301a, a high capacity can be achieved. This improves safety and allows for miniaturization and weight reduction.

[0362] In this embodiment, the first batteries 1301a and 1301b are connected in parallel. An example is shown, but you can connect three or more in parallel. Also, with the first battery 1301a If sufficient power can be stored, the first battery 1301b may not be necessary. By constructing a battery pack with a secondary battery, it is possible to extract a large amount of power. The number of secondary batteries may be connected in parallel, in series, or in parallel. After being connected, they may be further connected in series. Multiple secondary batteries are also called a battery pack.

[0363] Furthermore, in the case of rechargeable batteries used in vehicles, tools are used to cut off power from multiple rechargeable batteries. It has a service plug or circuit breaker that can cut off high voltage without any effort, and the first It is provided in the battery 1301a.

[0364] Furthermore, the power from the first batteries 1301a and 1301b is mainly used to rotate the motor 1304. It is used for the purpose of, but via the DC-DC circuit 1306, 42V automotive components (electric power supply It supplies power to the heater (1307, heater 1308, defogger 1309, etc.) and the rear wheels. Even when the rear motor 1317 is present, the first battery 1301a is connected to the rear motor 131 It is used to rotate the number 7.

[0365] Furthermore, the second battery 1311 is connected to 14V automotive components via the DC-DC circuit 1310. It supplies power to the audio system (1313), power windows (1314), lights (1315), etc. do.

[0366] Furthermore, the first battery 1301a will be explained using Figure 27(A).

[0367] Figure 27(A) shows an example where nine rectangular rechargeable batteries 1300 are combined into a single battery pack 1415. This shows that nine rectangular secondary batteries 1300 are connected in series, and one electrode is insulated or The other electrode is fixed with a fixing part 1413 made of an insulator, and the other electrode is fixed with a fixing part 1414 made of an insulator. This embodiment shows an example where the battery is fixed with fixing parts 1413 and 1414. The vehicle may be housed in a storage box (also called an enclosure). Since vibration or shaking is expected to be applied from the fixed parts 1413, 1414 Yes. It is preferable to secure multiple secondary batteries in a battery housing box or the like. Also, one of the batteries The pole is electrically connected to the control circuit unit 1320 by wiring 1421. The electrodes are electrically connected to the control circuit unit 1320 by wiring 1422.

[0368] Furthermore, the control circuit section 1320 uses a memory circuit that includes a transistor made of oxide semiconductor. It may be included. A charging control circuit having a memory circuit including an oxide semiconductor transistor. , or the battery control system, BTOS (Battery operating system) When referred to as em (or Battery oxide semiconductor) There is.

[0369] It is preferable to use a metal oxide that functions as an oxide semiconductor. For example, oxide 530 In-M-Zn oxide (where M is aluminum, gallium, yttrium, and copper) Vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium Molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten It is preferable to use a metal oxide such as one or more selected from magnesium, etc. In particular, the In-M-Zn oxide that can be applied as oxide 530 is CAAC-OS(CA xls Aligned Crystal Oxide Semiconductor) ,CAC-OS(Cloud-Aligned Composite Oxide Se It is preferable that the oxide 530 is In-G. α oxide and In-Zn oxide may also be used. CAAC-OS has multiple crystalline regions. Furthermore, these multiple crystalline regions are oxide semiconductors in which the c-axis is oriented in a specific direction. The specified direction refers to the thickness direction of the CAAC-OS film, the normal direction to the surface on which the CAAC-OS film is formed, Alternatively, it is the normal direction to the surface of the CAAC-OS film. Furthermore, a crystalline region is defined as a periodic region in the atomic arrangement. It is a region that possesses properties. Furthermore, if we consider the atomic arrangement as a lattice arrangement, then the crystalline region is defined as the lattice arrangement It is also a region where these are aligned. Furthermore, CAAC-OS has multiple crystal regions in the ab-plane direction. It has regions where multiple regions are connected, and these regions may have distortion. Distortion refers to multiple regions In regions where crystal regions are connected, there are regions with aligned lattice arrangements and other regions with aligned lattice arrangements. This refers to the point where the orientation of the grid arrangement changes between and . In other words, CAAC-OS is the c-axis. It is an oxide semiconductor that is oriented, but does not have a clear orientation in the ab-plane direction. -OS refers to, for example, a metal oxide whose constituent elements are preferably between 0.5 nm and 10 nm in size. Alternatively, it is a component of material that is unevenly distributed in sizes between 1 nm and 3 nm, or close to that size. Furthermore, in the following, in a metal oxide, one or more metal elements are unevenly distributed, and the metal element The region containing the element is 0.5 nm to 10 nm, preferably 1 nm to 3 nm. A mixture of similar or nearly identical sizes is also called a mosaic or patchy appearance.

[0370] Furthermore, CAC-OS is a system where the material separates into a first region and a second region, resulting in a mosaic effect. This results in a cloud-like structure, where the first region is distributed within the membrane (hereinafter also referred to as a cloud-like structure). Therefore, CAC-OS is a mixture of the first region and the second region. It is a composite metal oxide having the following configuration.

[0371] Here, In for the metal elements constituting CAC-OS in In-Ga-Zn oxide The atomic ratios of Ga and Zn are expressed as [In], [Ga], and [Zn] respectively. To note, for example, in CAC-OS in In-Ga-Zn oxide, the first region is This is the region where [In] is greater than the [In] in the composition of the CAC-OS film. The second region is the region where [Ga] is greater than the [Ga] in the composition of the CAC-OS film. Yes. Or, for example, in the first region, [In] is greater than [In] in the second region. This is a region where the [Ga] is large and smaller than the [Ga] in the second region. In the second region, [Ga] is greater than [Ga] in the first region, and [In This is a region smaller than [In] in the first region.

[0372] Specifically, the first region mentioned above is mainly composed of indium oxide, indium zinc oxide, etc. This is the region. Furthermore, the second region mentioned above includes gallium oxide, gallium zinc oxide, etc. This is the region in which is the principal component. In other words, the first region described above is called the region in which In is the principal component. It can be replaced. Furthermore, the second region mentioned above can be rephrased as the region with Ga as the main component. It is possible.

[0373] Furthermore, a clear boundary may not be observed between the first region and the second region described above.

[0374] For example, in CAC-OS in In-Ga-Zn oxide, energy-dispersive X-ray spectroscopy is used. Law(EDX:Energy Dispersive X-ray spectrosco The EDX mapping obtained using py) shows the region with In as the main component (the first region) It has a structure in which a region mainly composed of ) and a region mainly composed of Ga (the second region) are unevenly distributed and mixed. This can be confirmed.

[0375] When CAC-OS is used in a transistor, the conductivity is due to the first region and the second region The insulating properties resulting from this work in a complementary manner to enable the switching function (On / The function to turn it off can be added to CAC-OS. In other words, CAC-OS is In part of the material, it has conductive properties, and in part of the material, it has insulating properties, and the whole material It has the function of a semiconductor. By separating the conductive function and the insulating function, dual This allows for maximizing the functionality of the transistor. Therefore, CAC-OS is used in transistors. As a result, high on-current (I on ), high field-effect mobility (μ), and good switching This enables the implementation of a specific action.

[0376] Oxide semiconductors can take on diverse structures, each possessing different properties. One embodiment of the present invention Oxide semiconductors include amorphous oxide semiconductors, polycrystalline oxide semiconductors, a-like OS, and CA. It may have two or more of the following: C-OS, nc-OS, and CAAC-OS.

[0377] Furthermore, since it can be used in high-temperature environments, the control circuit section 1320 uses an oxide semiconductor. It is preferable to use a transistor. To simplify the process, control circuit section 13 20 may be formed using a unipolar transistor. An oxide semiconductor is used for the semiconductor layer. The transistor has a wider operating ambient temperature range than single-crystal Si, from -40°C to 150°C. Furthermore, the characteristics of secondary batteries change less when heated compared to single crystals. Transistors using oxide semiconductors The off-current of the zistor is below the detection limit regardless of temperature, even at 150°C, but single crystal S The off-current characteristics of an i-transistor are highly temperature-dependent. For example, at 150°C, single crystal Si transistors exhibit increased off-current, resulting in insufficient current on / off ratio. The circuit section 1320 can improve safety. Also, the positive electrode obtained in Embodiment 1 Combining active material 100 with a secondary battery using it as the positive electrode creates a synergistic effect on safety. Obtained. A secondary battery and control cell using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode. The circuit section 1320 can greatly contribute to eliminating accidents such as fires caused by secondary batteries.

[0378] The control circuit section 1320, which uses a memory circuit including an oxide semiconductor transistor, To address 10 causes of instability, such as microshorts, the automatic control device for secondary batteries... It can also be enabled. One of the functions to eliminate 10 causes of instability is overcharge prevention. Stop, overcurrent prevention, overheat control during charging, cell balancing in battery packs, over-discharge prevention, remaining charge indicator, Automatic control of charging voltage and current according to temperature, charging current control according to degradation level, micro-scaling Examples include detecting abnormal short-circuit behavior and predicting anomalies related to micro-shorts, and of these, a small portion... The control circuit unit 1320 has at least one function. Furthermore, the automatic control device for the secondary battery It can be miniaturized.

[0379] Furthermore, a microshort refers to a tiny short circuit inside a secondary battery. It's not a case of the positive and negative electrodes of the battery being short-circuited to the point where charging and discharging are impossible, but rather a very small short circuit. This refers to the phenomenon where a small short-circuit current flows. It occurs for a relatively short time and in a small area. Even in such locations, large voltage fluctuations occur, and these abnormal voltage values ​​affect subsequent estimations. There is a risk of this happening.

[0380] One of the causes of microshorts is that the positive electrode active material deteriorates due to multiple charge-discharge cycles. Due to the uneven distribution, localized current concentration occurs in parts of the positive and negative electrodes, causing the separator to... Some parts may stop functioning, or microscopic side effects may occur due to the generation of side reaction products. It is said that a short circuit has occurred.

[0381] In addition to detecting micro-shorts, the control circuit unit 1320 also detects the terminal voltage of the secondary battery. It can also be said that it detects and manages the charging and discharging state of the secondary battery. For example, to prevent overcharging, it can charge the battery. It is possible to turn off both the output transistor and the cutoff switch of the electrical circuit almost simultaneously. Cut.

[0382] Furthermore, an example of a block diagram of the battery pack 1415 shown in Figure 27(A) is shown in Figure 27(B). .

[0383] The control circuit unit 1320 includes at least a switch to prevent overcharging and a switch to prevent over-discharging. A switch section 1324 including a switch, and a control circuit 1322 that controls the switch section 1324, The control circuit unit 1320 has a voltage measuring unit for the first battery 1301a. The secondary battery has upper and lower voltage limits set, as well as an upper limit on the current from an external source and an upper limit on the output from an external source. It limits the current, etc. Within the range between the lower voltage limit and the upper voltage limit of the secondary battery, it can be used. If the voltage is within the recommended range, the switch unit 1324 will activate if it falls outside that range. It functions as a protection circuit. In addition, the control circuit unit 1320 controls the switch unit 1324. These can also be called protection circuits to prevent over-discharge and over-charge. For example, voltages that are likely to cause overcharging. When the control circuit 1322 detects this, the switch on the switch unit 1324 is turned off. The current is interrupted. Furthermore, a PTC element is provided in the charge / discharge path to control the current in accordance with the rise in temperature. A function to block the signal may be provided. In addition, the control circuit unit 1320 has an external terminal 1325 (+I It has N) and an external terminal 1326(-IN).

[0384] The switch section 1324 combines n-channel transistors and p-channel transistors. They can be combined to form a structure. The switch section 1324 uses single-crystal silicon. Not limited to switches with transistors, for example, Ge (germanium), SiGe (Silicon germanium), GaAs (Gallium arsenide), GaAlAs (Gallium aluminum) Indium arsenide (Nium), InP (Indium phosphide), SiC (Silicon carbide), ZnSe (Zinc selenide), GaN (gallium nitride), GaOx (gallium oxide; x is greater than 0) The switch section 1324 may be formed using a power transistor having a real number (or similar). Memory elements using OS transistors are stacked on top of circuits using Si transistors. Because it can be freely arranged, integration can be easily carried out. Since zistas can be manufactured using the same manufacturing equipment as Si transistors, It can be manufactured at low cost. That is, a control using an OS transistor on the switch section 1324 The circuit section 1320 can be stacked and integrated to form a single chip. Because the occupied volume of 1320 can be reduced, miniaturization becomes possible.

[0385] The first batteries, 1301a and 1301b, primarily supply power to 42V (high-voltage) in-vehicle equipment. The second battery 1311 supplies power to 14V (low-voltage) in-vehicle equipment. The second battery, 1311, is often a lead-acid battery because it is more cost-effective. Compared to lithium-ion rechargeable batteries, this battery has a higher self-discharge rate, which is called sulfation. It has the disadvantage of being prone to degradation due to the phenomenon. The second battery 1311 is a lithium-ion secondary battery This has the advantage of being maintenance-free, but for long-term use, for example, more than 3 years At higher levels, there is a risk of malfunctions occurring that cannot be detected during manufacturing. In particular, when the inverter is activated... If the second battery 1311 that is currently operating becomes inoperable, the first batteries 1301a, 130 To prevent the motor from failing to start even if there is remaining capacity in 1b, the second If battery 1311 is a lead-acid battery, power is supplied from the first battery to the second battery. And it is constantly being charged to maintain a fully charged state.

[0386] In this embodiment, both the first battery 1301a and the second battery 1311 are lithium An example of using a mu-ion secondary battery is shown. The second battery 1311 is a lead-acid battery or a solid-state battery. Alternatively, an electric double-layer capacitor may be used. For example, an all-solid-state battery of Embodiment 5 may be used. Good. High capacity can be achieved by using the all-solid-state battery of Embodiment 5 for the second battery 1311. This allows for miniaturization and weight reduction.

[0387] Furthermore, the regenerative energy from the rotation of the tire 1316 is transmitted to the motor 13 via the gear 1305. It is sent to 04 and controlled by the motor controller 1303 and battery controller 1302. The second battery 1311 is charged via circuit section 1321. Or battery control The first battery 1301a is charged from the roller 1302 via the control circuit unit 1320. Alternatively, the first battery can be controlled from the battery controller 1302 via the control circuit unit 1320. It is charged to battery 1301b. In order to efficiently charge with regenerative energy, the first battery It is desirable that the Ri1301a and Ri1301b models be capable of rapid charging.

[0388] The battery controller 1302 controls the charging voltage of the first batteries 1301a and 1301b. The charging current and other parameters can be set. The battery controller 1302 uses two The charging conditions can be set according to the charging characteristics of the next battery, enabling rapid charging.

[0389] Also, although not shown in the diagram, when connecting to an external charger, the charger's outlet or charging port The electrical connection cable is electrically connected to the battery controller 1302. Power supplied from the charger is transmitted to the first battery 1 via the battery controller 1302. Charges 301a and 1301b. Also, some chargers have a control circuit. Although the functions of the battery controller 1302 may not be used, the control is used to prevent overcharging. It is preferable to charge the first batteries 1301a and 1301b via the circuit section 1320. Also, the connection cable or the charger's connection cable may have a control circuit. The control circuit unit 1320 is an ECU (Electronic Control Unit). It is sometimes called an ECU. An ECU is a control unit installed in electric vehicles. It connects to the Area Network. CAN is used as the in-vehicle LAN. It is one of the serial communication standards. Furthermore, an ECU includes a microcomputer. ECUs use CPUs and GPUs.

[0390] External chargers installed at charging stations, etc., use 100V outlets or 200V outlets. There are also options such as contactless power supply and 3-phase 200V and 50kW. It can also be charged by receiving power from the charging facilities.

[0391] For rapid charging, a secondary battery capable of withstanding high-voltage charging is required to achieve short charging times. A pond is desired.

[0392] Furthermore, the secondary battery of this embodiment described above uses the positive electrode active material 100 obtained in Embodiment 1. By using it, it has a high-density positive electrode. Furthermore, graphene is used as a conductive additive, By increasing the thickness of the polar layer and thus the load-bearing capacity, the reduction in volume is suppressed, and the high volume is maintained, which is a synergistic effect. This makes it possible to realize secondary batteries with significantly improved electrical characteristics. This is especially useful for secondary batteries used in vehicles. This is effective, and without increasing the weight ratio of the secondary battery to the total weight of the vehicle, the driving range is increased. We can offer vehicles with a long range, specifically a driving range of 500km or more on a single charge.

[0393] In particular, the secondary battery of this embodiment described above uses the positive electrode active material 100 described in Embodiment 1. This allows the operating voltage of the secondary battery to be increased, and as the charging voltage increases, it can be used. The capacity can be increased. Also, the positive electrode active material 100 described in Embodiment 1 is positive By using it as an electrode, it is possible to provide a secondary battery for vehicles with excellent cycle characteristics.

[0394] Next, we will discuss an example in which a secondary battery, which is one aspect of the present invention, is implemented in a vehicle, typically a transport vehicle. I will explain.

[0395] Furthermore, the secondary battery shown in any one of Figures 14(D), 16(C), or 27(A) is used in the vehicle. When installed, it can be used in hybrid vehicles (HV), electric vehicles (EV), or plug-in hybrid vehicles. It enables the realization of next-generation clean energy vehicles such as plug-in hybrid vehicles (PHVs). Furthermore, agricultural machinery... Motorized bicycles including electric assist bicycles, motorcycles, electric wheelchairs, electric carts, small Or large ships, submarines, aircraft such as fixed-wing and rotary-wing aircraft, rockets, artificial satellites, space exploration The present invention also allows for the installation of secondary batteries in transport vehicles such as aircraft, planetary probes, and spacecraft. One embodiment of the secondary battery can be a high-capacity secondary battery. Therefore, one embodiment of the present invention is a second The next battery is suitable for miniaturization and weight reduction, and can be suitably used in transport vehicles.

[0396] Figures 28(A) to (D) illustrate a transport vehicle using one embodiment of the present invention. The automobile 2001 shown in 8(A) is an electric vehicle that uses an electric motor as a power source for driving. It is a motor vehicle. Alternatively, it uses an electric motor and an engine as appropriate as power sources for propulsion. It is a hybrid vehicle that is capable of being. When a secondary battery is installed in the vehicle, the practical form Install one or more of the secondary batteries shown in Figure 4. The locomotive 2001 has a battery pack 2200, which connects multiple secondary batteries. It has a secondary battery module. Furthermore, a charge control is electrically connected to the secondary battery module. It is preferable to have a device.

[0397] Furthermore, the automobile 2001 has a secondary battery that can be plugged in or contactless supplied. The device can be charged by receiving power from an external charging facility using an electrical system, etc. Therefore, charging methods and connector standards are specified by CHAdeMO (registered trademark) and Combo, etc. The method can be carried out as appropriate. The secondary battery can be charged at a charging station located in a commercial facility. It could also be a household power supply. For example, external power supply via plug-in technology. This allows charging of the battery storage device installed in the automobile 2001. Charging is performed by AC / DC. This can be done by converting AC power to DC power via a conversion device such as a converter.

[0398] Although not shown in the diagram, a power receiving device is mounted on the vehicle, and power is supplied wirelessly from a ground-based power transmission device. It can also be charged by doing so. In this contactless power supply method, power transmission equipment is installed in roads or exterior walls. By incorporating this, charging can be performed not only when the vehicle is stopped but also while it is in motion. Furthermore, this contactless power supply... Using this method, power can be transmitted and received between two vehicles. Furthermore, outside the vehicle Solar cells may be installed in the battery compartment to charge the secondary battery when the vehicle is stopped or in motion. For power supply via contact, electromagnetic induction or magnetic resonance methods can be used.

[0399] Figure 28(B) shows a large transport vehicle equipped with an electrically controlled motor as an example of a transport vehicle. This shows vehicle 2002. The secondary battery module of transport vehicle 2002 has a nominal voltage of, for example, 3. Four rechargeable batteries with a voltage between 0V and 5.0V are used as cell units, and 48 cells are connected in series. The maximum voltage is set to 70V. The secondary batteries constituting the secondary battery module of battery pack 2201. Aside from differences in the number of elements, it has the same functions as Figure 28(A), so the explanation will be omitted.

[0400] Figure 28(C) shows, as an example, a large transport vehicle 2003 equipped with an electrically controlled motor. This indicates that the secondary battery module of the transport vehicle 2003 has a nominal voltage of, for example, 3.0V or higher. The maximum voltage will be 600V, achieved by connecting more than 100 secondary batteries with a voltage of 5.0V or less in series. Therefore, A secondary battery with small variation in characteristics is required. The positive electrode active material 100 described in Embodiment 1 By using a secondary battery with a positive electrode, it is possible to manufacture a secondary battery with stable battery characteristics. This allows for low-cost mass production from a yield perspective. Also, battery pack 2 Aside from the number of secondary batteries that make up the 202 secondary battery module, it is the same as Figure 28(A) Since it has similar functionality, I will omit the explanation.

[0401] Figure 28(D) shows, as an example, aircraft 2004 having a fuel-burning engine. The aircraft 2004 shown in Figure 28(D) has landing gear for takeoff and landing, so it can be transported by a vehicle. It can be said that it is part of a secondary battery module, which is constructed by connecting multiple secondary batteries. It has a battery pack 2203 that includes a joule and a charge control device.

[0402] The secondary battery module of the aircraft 2004 uses, for example, eight 4V secondary batteries connected in series. The maximum voltage is set to 2V. The secondary batteries that make up the secondary battery module of the battery pack 2203 Aside from differences in the number of elements, it has the same functions as Figure 28(A), so the explanation will be omitted.

[0403] This embodiment can be used in appropriate combination with other embodiments.

[0404] (Embodiment 7) In this embodiment, Figure 29 shows an example of implementing a secondary battery, which is one aspect of the present invention, in a building. This will be explained using (A) and Figure 29(B).

[0405] The house shown in Figure 29(A) is an energy storage device 2612 having a secondary battery, which is one embodiment of the present invention. The solar panel 2610 is included. The energy storage device 2612 is connected to the solar panel 2610. They are electrically connected via wire 2611, etc. Also, the energy storage device 2612 and the ground-mounted charging The electrical device 2604 may be electrically connected. The power obtained from the solar panel 2610 is The power stored in the power storage device 2612 can be charged. The secondary battery of the vehicle 2603 can be charged via the charging device 2604. The electrical device 2612 is preferably installed in the underfloor space. This allows for effective use of the space above the floor. Alternatively, the energy storage device 2612 is located on the floor. It can also be installed on top.

[0406] The electricity stored in the energy storage device 2612 can also be used to power other electronic devices in the house. Yes, it is possible. Therefore, even when power cannot be supplied from the commercial power source due to a power outage, the present invention By using a power storage device 2612 according to one embodiment as an uninterruptible power supply, the use of electronic devices becomes possible. It becomes Noh.

[0407] Figure 29(B) shows an example of an energy storage device 700 according to one aspect of the present invention. As such, in the underfloor space 796 of the building 799, there is an energy storage device 791 according to one aspect of the present invention. It is installed. Furthermore, the power storage device 791 may be equipped with the control circuit described in Embodiment 6. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode is stored in an energy storage device 791. By using it, a synergistic effect on safety can be obtained. Control circuit described in Embodiment 6 Furthermore, the secondary battery using the positive electrode active material 100 described in Embodiment 1 as the positive electrode has a secondary battery The energy storage device 791 can greatly contribute to eliminating accidents such as fires.

[0408] The energy storage device 791 is equipped with a control device 790, and the control device 790 is connected by wiring. And, the distribution board 703, the energy storage controller 705 (also called the control device), and the display unit 706 It is electrically connected to router 709.

[0409] Power is supplied from the commercial power supply 701 to the distribution panel 703 via the service drop connection section 710. Furthermore, power is supplied to the distribution board 703 from the energy storage device 791 and the commercial power supply 701. The distribution board 703 distributes the power received to the general load 707 and via outlets (not shown). It supplies power to the energy storage system load 708.

[0410] General load 707 is, for example, electrical equipment such as televisions and personal computers, and storage Electrical load 708 is, for example, electrical equipment such as a microwave oven, refrigerator, or air conditioner.

[0411] The energy storage controller 705 includes a measurement unit 711, a prediction unit 712, and a planning unit 713. The measurement unit 711 measures the general load 707 and the energy storage system during a day (for example, from 0:00 to 24:00). It has a function to measure the amount of electricity consumed by the load 708. In addition, the measuring unit 711 is a power storage device It has the function of measuring the amount of electricity from the 791 unit and the amount of electricity supplied from the commercial power supply 701. It may also be necessary to predict the general load 707 and the energy storage system load 708 during the day. Based on the amount of electricity consumed, during the following day, the general load 707 and the energy storage system load 708 It has a function to predict the amount of electricity demanded to be consumed. In addition, the planning unit 713 has a function to predict the amount of electricity demanded to be consumed. It has the function of planning the charging and discharging of the energy storage device 791 based on the predicted amount of electricity demand.

[0412] The power consumed by the general load 707 and the energy storage system load 708 as measured by the measurement unit 711 The quantity can be checked by the display unit 706. Also, via the router 709, tele This can also be checked in electrical devices such as computers and personal computers. Furthermore, It can also be verified via router 709 using mobile electronic devices such as smartphones and tablets. It is possible to do so using the display unit 706, electrical equipment, and portable electronic terminals, and the prediction unit 71 You can also check the predicted electricity demand for each time period (or hourly) as predicted by 2. .

[0413] This embodiment can be used in appropriate combination with other embodiments.

[0414] (Embodiment 8) This embodiment shows an example of mounting an energy storage device according to one aspect of the present invention on a motorcycle or bicycle. .

[0415] Furthermore, Figure 30(A) shows an example of an electric bicycle using a power storage device according to one embodiment of the present invention. An energy storage device according to one embodiment of the present invention can be applied to the electric bicycle 8700 shown in 30(A). One embodiment of the present invention is a power storage device that includes, for example, a plurality of storage batteries and a protection circuit.

[0416] The electric bicycle 8700 is equipped with a power storage device 8702. The power storage device 8702 provides the rider with an assist It can supply electricity to the motor that is being struck. Also, the energy storage device 8702 is portable. Figure 30(B) shows the device after it has been removed from the bicycle. Also, the energy storage device 8702 The energy storage device according to one aspect of the present invention has multiple storage batteries 8701 built in, and the battery The battery level and other information can be displayed on the display unit 8703. The energy storage device 8702 is also configured to display the remaining battery level and other information. A control circuit 870 capable of controlling the charging of a secondary battery or detecting abnormalities is shown as an example in Embodiment 6. It has 4. The control circuit 8704 is electrically connected to the positive and negative terminals of the storage battery 8701. It is present. In addition, the control circuit 8704 has a small solid secondary as shown in Figures 26(A) and 26(B). A battery may be provided. Control the small solid-state rechargeable battery shown in Figures 26(A) and 26(B). By providing this in circuit 8704, the data in the memory circuit of the control circuit 8704 can be retained for a long time. It can also supply power to do so. Also, the positive electrode active material 10 obtained in Embodiment 1 By combining it with a secondary battery that uses 0 as the positive electrode, a synergistic effect on safety can be obtained. A secondary battery and control circuit 8704 using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode. This can greatly contribute to eliminating accidents such as fires caused by secondary batteries.

[0417] Furthermore, Figure 30(C) shows an example of a motorcycle using an energy storage device according to one embodiment of the present invention. Figure 30 The scooter 8600 shown in (C) includes a power storage device 8602, side mirrors 8601, and turn signals. It is equipped with a lamp 8603. The energy storage device 8602 can supply electricity to the turn signal lamp 8603. Yes, it is possible. Furthermore, multiple secondary batteries can be made using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode. The housed energy storage device 8602 can have a high capacity, which contributes to miniaturization. .

[0418] Furthermore, the scooter 8600 shown in Figure 30(C) has a power storage device 860 in the under-seat storage compartment 8604. It can store 2. The power storage device 8602 can store even if the under-seat storage 8604 is small. It can be stored in the under-seat storage compartment 8604.

[0419] (Embodiment 9) This embodiment describes an example in which a secondary battery, which is one aspect of the present invention, is mounted in an electronic device. To do so. Electronic devices that implement secondary batteries include, for example, television equipment (television, or television). (also called a revision receiver), monitors for computers, digital cameras, digital Video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices) ), portable game consoles, personal digital assistants, sound playback devices, large game machines such as pachinko machines, etc. Examples include notebook personal computers and tablet devices. These include e-readers and mobile phones.

[0420] Figure 31(A) shows an example of a mobile phone. The mobile phone 2100 has a casing 2101 In addition to the display unit 2102 incorporated into it, there are operation buttons 2103, an external connection port 2104, and It is equipped with a speaker 2105, a microphone 2106, etc. Note that the mobile phone 2100 is secondary It has a battery 2107. The positive electrode active material 100 described in Embodiment 1 is used as the positive electrode. By incorporating the next battery 2107, high capacity can be achieved, and the casing can be made smaller, saving space. This allows for a configuration that can adapt to changes in the environment.

[0421] The 2100 mobile phone offers mobile phone calls, email, document viewing and creation, music playback, and internet connectivity. It can run various applications such as internet communication and computer games. .

[0422] The operation button 2103 is used for setting the time, as well as turning the power on and off, and turning wireless communication on and off. It has various functions such as operation, silent mode activation and deactivation, and power saving mode activation and deactivation. This can be done. For example, the operating system built into the mobile phone 2100 The system also allows you to freely configure the function of the operation button 2103.

[0423] Furthermore, the mobile phone 2100 is capable of performing standardized short-range wireless communication. For example, by communicating with a wireless headset, hands-free communication is possible. They can also talk.

[0424] Furthermore, the mobile phone 2100 is equipped with an external connection port 2104, and has a connector for connecting to other information terminals. Data can be exchanged directly via this. Also, via external connection port 2104 It can also be charged. Note that charging is performed wirelessly without using the external connection port 2104. This may also be done by means of.

[0425] The mobile phone 2100 preferably has a sensor. For example, a fingerprint sensor. Human body sensors such as pulse sensors and body temperature sensors, as well as touch sensors, pressure sensors, and acceleration sensors. It is preferable that the following are installed:

[0426] Figure 31(B) shows an unmanned aerial vehicle 2300 having multiple rotors 2302. The 2300 is sometimes called a drone. The unmanned aerial vehicle 2300 is one aspect of the present invention. It has a secondary battery 2301, a camera 2303, and an antenna (not shown). Unmanned aerial vehicle The 2300 can be remotely controlled via an antenna. The positive electrode obtained in Embodiment 1 Secondary batteries using active material 100 as the positive electrode have high energy density and high safety, so It can be used safely for extended periods and is suitable as a secondary battery for use in the Unmanned Aerial Vehicle 2300. It is suitable.

[0427] Figure 31(C) shows an example of a robot. The robot 6400 shown in Figure 31(C) is , secondary battery 6409, illuminance sensor 6401, microphone 6402, upper camera 640 3. Speaker 6404, display unit 6405, lower camera 6406, and obstacle sensor 640 7. It is equipped with a moving mechanism 6408, a computing device, etc.

[0428] Microphone 6402 has the function of detecting the user's voice and ambient sounds, etc. Speaker 6404 has the function of emitting sound. Robot 6400 has a microphone Using the 6402 and speaker 6404, communication with the user is possible. It is possible.

[0429] The display unit 6405 has the function of displaying various information. The robot 6400 is used by The desired information can be displayed on the display unit 6405. The display unit 6405 is touch It may also be equipped with a panel. Furthermore, the display unit 6405 is a detachable information terminal. It is also possible to install it in a fixed position on the robot 6400 for charging and data transfer. Make it possible.

[0430] The upper camera 6403 and lower camera 6406 are used to image the area around the robot 6400. It has the ability to move the robot 6407 using the moving mechanism 6408. Robot 64 can detect the presence or absence of obstacles in the direction of travel as it moves forward. 00 uses the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 It can perceive its surroundings and move safely.

[0431] The robot 6400 has a secondary battery 6409 according to one aspect of the present invention and a semiconductor in its internal region. The apparatus or electronic components are provided. The positive electrode active material 100 obtained in Embodiment 1 is used as the positive electrode. Rechargeable batteries have high energy density and high safety, making them safe for long periods of time. It can be used and is suitable as a secondary battery 6409 to be mounted on the robot 6400.

[0432] Figure 31(D) shows an example of a cleaning robot. The cleaning robot 6300 has a housing 63 01 Display unit 6302 located on the top surface, multiple cameras 6303 located on the side, brush It includes 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. (as shown in the figure) Although not shown, the 6300 cleaning robot is equipped with wheels, a suction nozzle, etc. The robot 6300 moves autonomously, detects the debris 6310, and removes it from the suction port located on its underside. It can suck up dust.

[0433] For example, the cleaning robot 6300 analyzes images captured by the camera 6303 to identify walls, furniture, etc. It can also determine the presence or absence of obstacles such as steps. Furthermore, image analysis can detect wiring, etc. If an object that may become entangled in the brush 6304 is detected, the rotation of the brush 6304 will be stopped. This is possible. The cleaning robot 6300 has a secondary battery 6 according to one aspect of the present invention in its internal region. The positive electrode active material 10 obtained in Embodiment 1 comprises 306 and a semiconductor device or electronic component. Secondary batteries using 0 as the positive electrode have high energy density and high safety, and can be used for long periods of time. It allows for safe use over long periods and is used as the secondary battery 6306 for the cleaning robot 6300. It is suitable.

[0434] Figure 32(A) shows an example of a wearable device. A wearable device is an electric device. It uses a secondary battery as a power source. Furthermore, it is designed to withstand water use during everyday or outdoor activities. To enhance water resistance, in addition to wired charging where the connector part is exposed, There is a demand for wearable devices that can also be charged via cable.

[0435] For example, in a glasses-type device 4000 as shown in Figure 32(A), a secondary [of the present invention] is provided. It can be equipped with a battery. The glasses-type device 4000 consists of frame 4000a and display It has section 4000b. A rechargeable battery is mounted in the temple section of the curved frame 4000a. This results in a lightweight, well-balanced, and long-lasting glasses-type device. It can be set to 4000. The positive electrode active material 100 obtained in Embodiment 1 is used as the positive electrode. The rechargeable battery has a high energy density and a configuration that can accommodate space saving due to the miniaturization of the housing. This can be achieved.

[0436] Furthermore, the headset-type device 4001 is equipped with a secondary battery according to one aspect of the present invention. This is possible. The headset-type device 4001 includes at least a microphone unit 4001a and a frame It has a flexible pipe 4001b and an earphone section 4001c. A secondary battery can be installed inside 001b or inside the earphone section 4001c. Embodiment 1 A secondary battery using the positive electrode active material 100 obtained in this way as the positive electrode has a high energy density, and the housing This allows for a configuration that can accommodate space-saving requirements resulting from miniaturization.

[0437] Furthermore, a secondary battery according to one aspect of the present invention is incorporated into a device 4002 that can be directly attached to the body. It can be mounted. Inside the slim housing 4002a of Device 4002, the secondary battery 400 2b can be provided. The positive electrode active material 100 obtained in Embodiment 1 is used as the positive electrode. The next battery has a high energy density and a configuration that can accommodate space saving due to the miniaturization of the housing. It can be achieved.

[0438] Furthermore, a secondary battery according to one aspect of the present invention is mounted on a device 4003 that can be attached to clothing. This is possible. Inside the slim housing 4003a of device 4003, the secondary battery 4003b A positive electrode active material 100 obtained in Embodiment 1 is used as the positive electrode in a secondary electric field. The pond has a high energy density, enabling a configuration that can accommodate space savings due to the miniaturization of the enclosure. It is possible.

[0439] Furthermore, a secondary battery according to one aspect of the present invention can be mounted on the belt-type device 4006. The belt-type device 4006 consists of a belt section 4006a and a wireless power supply / receiving section 40 It has 06b, and a secondary battery can be mounted in the internal region of the belt portion 4006a. A secondary battery using the positive electrode active material 100 obtained by method 1 as the positive electrode has a high energy density. This allows for a configuration that can accommodate space savings resulting from the miniaturization of the enclosure.

[0440] Furthermore, a secondary battery according to one aspect of the present invention can be mounted in the wristwatch-type device 4005. The wristwatch-type device 4005 has a display unit 4005a and a belt unit 4005b, A secondary battery can be installed in the indicator section 4005a or the belt section 4005b. A secondary battery using the positive electrode active material 100 obtained in state 1 as the positive electrode has a high energy density, and the housing This allows for a configuration that can accommodate space-saving requirements resulting from miniaturization of the device.

[0441] The display unit 4005a displays not only the time, but also various other information such as incoming emails and phone calls. It is possible.

[0442] Furthermore, the wristwatch-type device 4005 is a wearable device that is worn directly on the wrist. Therefore, sensors may be installed to measure the user's pulse, blood pressure, etc. User's exercise volume It also allows for the accumulation of health-related data and the management of health.

[0443] Figure 32(B) shows a perspective view of the wristwatch-type device 4005 after it has been removed from the arm.

[0444] A side view is also shown in Figure 32(C). Figure 32(C) shows the secondary battery 913 inside the internal region. This shows how it is stored. The secondary battery 913 is the secondary battery shown in Embodiment 4. The secondary battery 913 is located in a position overlapping with the display unit 4005a, and is high density and high capacity. It can be used in small quantities, and is also small and lightweight.

[0445] Since the wristwatch-type device 4005 is required to be small and lightweight, By using the positive electrode active material 100 obtained in Embodiment 1 as the positive electrode of the secondary battery 913, high energy This allows for the creation of a compact secondary battery 913 with high energy density.

[0446] This embodiment can be implemented in appropriate combination with other embodiments. [Examples]

[0447] This example shows the results of electron microscope observation of a positive electrode according to one embodiment of the present invention.

[0448] First, a positive electrode active material according to one embodiment of the present invention was prepared by the manufacturing method shown in Figure 1.

[0449] <Fabrication of positive electrode active material> As a pre-synthesized composite oxide having lithium, transition metal M, and oxygen, Japan Prepare lithium cobalt oxide particles (product name: Cellseed C-10N) manufactured by Chemical Industry Co., Ltd. (Step S14)

[0450] Next, lithium fluoride was used as the fluorine source, and magnesium fluoride as the magnesium source. Prepare the materials so that the molecular weight ratio is lithium fluoride:magnesium fluoride = 1:3 (step Step S21), crushing and mixing are performed (Step S22) to obtain mixture 902 (Step S twenty three).

[0451] Next, lithium cobalt oxide and mixture 902 are used to determine the cobalt contained in lithium cobalt oxide. When the number of atoms of fluoride is set to 100, the number of magnesium fluoride molecules contained in mixture 902 is... Prepare the mixture to make a total of 1, mix it (step S41), and obtain mixture 903 (step S4 2).

[0452] Next, the mixture 903 was placed in an alumina container, covered with a lid, and placed in a muffle furnace. Mixture 903 was heated (step S43). The heating conditions were 900°C for 20 hours in an oxygen atmosphere. I was worried.

[0453] Next, the heated second mixture, nickel hydroxide, and aluminum hydroxide are mixed with cobalt. When the number of cobalt atoms in lithium trioxide is set to 100, the number of nickel hydroxide molecules The mixture was prepared so that the molecular weight of the aluminum hydroxide was 0.5. (P S31). Next, the nickel hydroxide and aluminum hydroxide prepared in step S31 and the heated mixture Mixture 903 and (step S61) were mixed to obtain mixture 904 (step S62).

[0454] Next, the mixture 904 was placed in an alumina container, covered with a lid, and placed in a muffle furnace. Compound 904 was heated (step S63) to produce a positive electrode active material according to one embodiment of the present invention. Here, the heat treatment is not performed in two separate heating steps, S63 and S67. The heating conditions were as follows: 850°C for 10 hours in an oxygen atmosphere. Ta.

[0455] <Fabrication of the positive electrode> Next, a positive electrode was fabricated using the prepared positive electrode active material. (Positive electrode active material, AB, and PVDF) A slurry was prepared by mixing the positive electrode active material AB:PVDF in a weight ratio of 95:3:2. The slurry was then coated onto a 20 μm thick aluminum current collector. N was used as the solvent for the slurry. I used MP.

[0456] After coating the current collector with slurry, the solvent was evaporated. Then, pressurization was applied at 210 kN / m. After that, further pressurization was applied at 1467 kN / m. The positive electrode was obtained through the above process. Fabrication The amount of support in the positive electrode was approximately 6 mg / cm³. 2 The density of the positive electrode active material layer was approximately 3 The concentration was 0.9 g / cc.

[0457] <Manufacturing of secondary batteries> Next, using the fabricated positive electrode, a CR2032 type (20mm diameter, 3.2mm height) We fabricated an IN-type battery cell.

[0458] Lithium metal was used for the counter electrode.

[0459] The electrolyte in the electrolyte solution is 1 mol / L lithium hexafluoride phosphate (LiPF6). The electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC). A mixture of C:DEC in a volume ratio of 3:7 is then mixed with vinylene carbonate (VC). We used a product with wt% added.

[0460] A 25 μm thick polypropylene was used for the separator.

[0461] The positive electrode and negative electrode cans were made of stainless steel (SUS).

[0462] <Cycle Characteristics> Next, the cycle characteristics of the fabricated secondary battery were evaluated. Charging was performed at a rate of 0.5C with an upper limit of 4. After constant current charging up to 7V, constant voltage charging was performed at 4.7V up to a rate of 0.05C. Discharge was performed at a constant current discharge rate of 0.5C down to a lower limit of 2.5V. 200mA / g The C-rate was calculated. The measurement was performed at 45°C.

[0463] The cycle characteristics are shown in Figure 33. The horizontal axis represents the number of cycles, and the vertical axis represents the discharge capacity. 50 cycles After the cycle, the discharge capacity decreased to less than 40% of that of the first cycle.

[0464] <Battery Disassembly> The secondary battery, which had undergone 50 charge-discharge cycles, was disassembled, and the positive electrode was removed. The dismantling was carried out under an argon atmosphere. After dismantling, the parts were cleaned with DMC, and then the solvent was evaporated. Furthermore, observations were also made at the stage after the positive electrode was fabricated, before it was incorporated into the secondary battery.

[0465] <SEM observation> Next, the positive electrode taken out by disassembling the secondary battery was subjected to scanning electron microscopy (SEM) observation. FIG. 34(A) shows an SEM image of the positive electrode of the secondary battery after 50 cycles. FIG. 34 (B) shows an SEM image of the positive electrode before being incorporated into the secondary battery. For the SEM observation, a Hitachi High-Tech Corporation manufactured scanning electron microscope apparatus SU8030 was used for the observation.

[0466] Next, the positive electrode was subjected to cross-section processing with FIB (Focused Ion Beam), and the cross section of the positive electrode was observed by SEM. By repeating the cross-section processing with FIB and the SEM observation, three-dimensional information of the structure can be obtained. Note that Hitachi High-Tech manufactured XVision2 10B was used for the FIB processing and the SEM observation.

[0467] FIG. 35(A) shows an SEM image of the top surface of the positive electrode of the secondary battery after 50 cycles. FIG. 35(B) is a cross-sectional view of the broken line portion in FIG. 35(A). Further, FIG. 35(C) is an enlarged view of the portion surrounded by the square frame in FIG. 35(B) . FIG. 35(C) shows pits 90a, 90b, and 90 c.

[0468] FIG. 36(A) is the same SEM image as FIG. 35(A), but the broken line portion is different. FIG. 36(B) is a cross-sectional view of the broken line portion in FIG. 36(A). That is, FIG. 36(B) is an image obtained by shifting the position of the cross section from FIG. 35 (B). Further, FIG. 36(C) is an enlarged view of the portion surrounded by the square frame in FIG. 36(B). FIG. 36(C) shows pits 90d, 90e, and a crack 91 a. a.

[0469] FIG. 37(A) is the same SEM image as FIG. 35(A) and FIG. 36(A), but the broken line portion is different re. FIG. 37(B) is a cross-sectional view of the broken line portion in FIG. 37(A). That is, FIG. 37 (B) is an image with the cross-sectional position shifted from FIG. 35(B) and FIG. 36(B). Also, FIG. 3 7(C) is an enlarged view of the portion enclosed by the square frame in FIG. 37(B). FIG. 37(C) shows pi ts 90f and 90g, and a cavity 92a.

[0470] FIG. 38(A) shows an SEM image of the top surface of the positive electrode before being incorporated into the secondary battery. FIG. 38(B) is a cross-sectional view of the broken line portion in FIG. 38(A). Further, FIG. 38(C) and (D) are respectively enlarged views of two portions enclosed by the square frames in FIG. 38 (B). FIG. 38(D) shows a crac k 91b.

[0471] As described above, when the positive electrode after 50 cycles was observed, pits, cracks and cavitie s were observed.

[0472] <STEM Observation> Next, the cross section of the positive electrode of the secondary battery after 50 cycles was observed with a scanning transmission electron microscope (STEM) . Processing of the sample for cross-sectional observation was performed using FIB. FIG. 39(A ) shows a transmission electron image (TE image), and FIG. 39(B) shows a secondary electron image (SE image) of the same locatio n, respectively. FIG. 39(C) is an enlarged view of the portion enclosed by the square frame in FIG. 39(B). A H itachi High-Technologies Corporation HD-2700 scanning transmission electron microscope was used for the STEM observation.

[0473] The width of the pit was observed at the position indicated by the arrow in FIG. 39(C). The results are shown in Table 1 .

[0474] [Table 1]

[0475] The width of the pits was in the range of approximately 10 nm to 25 nm.

[0476] <EDX analysis> Next, the positive electrode of the secondary battery after 50 cycles was analyzed using energy dispersive X-ray spectroscopy (EDX :Energy Dispersive X-ray spectroscopy) for evaluation.

[0477] FIG. 40(A) shows a cross-sectional STEM image of the positive electrode shown in FIG. 39(B). FIG. 40(B) is an enlarged view of the portion enclosed by the square frame in FIG. 40(A).

[0478] EDX mapping of the region shown in FIG. 40(B) is shown in FIGS. 41(A) to (C). FIG. 41(A) shows the EDX mapping of magnesium, FIG. 41(B) shows that of aluminum, and FIG. 41(C) shows that of cobalt , respectively. For the EDX analysis, HD-2700 manufactured by Hitachi High-Tech was used. The acceleration voltage was set to 200 kV. The EDX mapping suggested that magnesium and aluminum are present in at least a part of the surface layer portion of the positive electrode active material particles . .

Description of Reference Signs

[0479] 100 Positive electrode active material 300 Secondary battery 301 Positive electrode can 302 Negative electrode can 303 Gasket 304 Positive electrode 305 Positive electrode current collector 306 Positive electrode active material layer 307 Negative electrode 308 Negative electrode current collector 309 Negative electrode active material layer 310 Separator 312 Washer 313 Ring-shaped insulator 322 Spacer 400 Secondary battery 410 Positive electrode 411 Cathode active material 413 Positive electrode current collector 414 Cathode active material layer 420 Solid electrolyte layer 421 Solid electrolyte 430 negative electrode 431 Negative electrode active material 433 Negative electrode current collector 434 Negative electrode active material layer 501 Positive electrode current collector 502 Positive electrode active material layer 503 Positive electrode 504 Negative electrode current collector 505 Negative electrode active material layer 506 negative electrode 507 Separator 508 Electrolyte 509 Exterior 509a Exterior 509b Exterior 510 Positive lead electrode 511 Negative lead electrode 513 Secondary battery 514 terminals 515 Seal 516 Seal 517 Antenna 519 layers 529 labels 530 Oxides 531 Rechargeable Battery Pack 540 Circuit Boards 550 Current collector 551 Meanwhile 552 The following 553 Acetylene Black 554 Graphene 555 Carbon nanotubes 561 Active material 562 Active material 590 Control Circuit 590a Circuit System 590b Circuit System 600 Secondary battery 601 Positive Cap 602 Battery Can 603 Positive terminal 604 Positive electrode 605 Separator 606 negative electrode 607 Negative terminal 608 Insulating board 609 Insulating board 611 PTC element 613 Safety valve mechanism 614 Conductive plate 615 Energy Storage System 616 Secondary battery 620 Control Circuit 621 Wiring 622 Wiring 623 Wiring 624 Conductors 625 Insulator 626 Wiring 627 Wiring 628 Conductive plate 700 Energy storage device 701 Commercial power supply 703 Distribution board 705 Energy Storage Controller 706 Display 707 General load 708 Energy storage system load 709 Router 710 Service drop connection section 711 Measurement Unit 712 Prediction Section 713 Planning Department 750a positive electrode 750b solid electrolyte layer 750c negative pole 751 Electrode Plate 752 Insulating tube 753 Electrode Plate 761 Lower member 762 Upper member 764 Wing nut 765 O-ring 766 Insulator 770a Package component 770b Package components 770c Package components 771 External electrode 772 External electrode 773a Electrode layer 773b Electrode layer 790 Control Unit 791 Energy storage device 796 Underfloor space 799 buildings 902 mixture 903 mixture 904 Mixture 911a terminal 911b terminal 913 Secondary battery 930 cabinets 930a enclosure 930b enclosure 931 negative electrode 931a Negative electrode active material layer 932 Positive electrode 932a Cathode active material layer 933 Separator 950 Wound body 950a Wound body 951 terminal 952 terminals 1300 rectangular rechargeable battery 1301a Battery 1301b Battery 1302 Battery Controller 1303 Motor Controller 1304 Motor 1305 Gear 1306 DC-DC Circuit 1307 Electric Power Steering 1308 Heater 1309 Defogger 1310 DC-DC Circuit 1311 Battery 1312 Inverter 1313 Audio 1314 Power windows 1315 Lamps 1316 Tires 1317 Rear Motor 1320 Control circuit section 1321 Control circuit section 1322 Control Circuit 1324 Switch section 1325 External terminals 1326 External terminals 1413 Fixed part 1414 Fixed part 1415 Battery Pack 1421 Wiring 1422 Wiring 2001 Automobile 2002 Transport Vehicle 2003 Transport Vehicles 2004 aircraft 2100 Mobile Phone 2101 enclosure 2102 Display section 2103 Operation Buttons 2104 External connection port 2105 Speaker 2106 Mike 2107 Secondary battery 2200 Battery Pack 2201 Battery Pack 2202 Battery Pack 2203 Battery Pack 2300 Unmanned Aircraft 2301 Secondary battery 2302 Rotor 2303 Camera 2603 Vehicles 2604 Charging device 2610 Solar Panel 2611 Wiring 2612 Energy storage device 4000 Glasses-type devices 4000a frame 4000b Display section 4001 Headset-type device 4001a Microphone section 4001b Flexible pipe 4001c Earphone section 4002 Device 4002a enclosure 4002b secondary battery 4003 device 4003a enclosure 4003b secondary battery 4005 Wristwatch-type device 4005a Display section 4005b Belt section 4006 Belt-type device 4006a Belt section 4006b Wireless power supply and receiving unit 6300 Cleaning Robot 6301 enclosure 6302 Display section 6303 Camera 6304 Brush 6305 Operation Buttons 6306 Secondary battery 6310 Garbage 6400 robots 6401 Illuminance Sensor 6402 Microphone 6403 Top camera 6404 Speaker 6405 Display section 6406 Lower camera 6407 Obstacle Sensor 6408 Moving mechanism 6409 Secondary battery 8600 Scooter 8601 Side Mirror 8602 Energy Storage Device 8603 Turn signal light 8604 Under-seat storage 8700 Electric Bicycle 8701 Storage Battery 8702 Energy storage device 8703 Display section 8704 Control Circuit

Claims

[Claim 1] A first step is to mix lithium fluoride, a second material having magnesium, and a third material which is a metal oxide having lithium and cobalt to produce a first mixture. A second step involves placing the first mixture into a first container, covering the first container with a lid, and performing a first heating for a temperature range of 742°C to 950°C and for a range of 1 hour to 100 hours to produce a second mixture. A third step involves mixing the second mixture with a fourth material having nickel, and then further mixing a fifth material having aluminum with a sixth material having zirconium to produce a third mixture. A fourth step is to perform a second heating of the third mixture at a temperature range of 350°C or more and less than 600°C, and for a period of 1 hour or more and 100 hours or less, in order to produce a fourth mixture. The fifth step involves placing the fourth mixture into a second container, covering the second container with a lid, and performing a third heating for a temperature range of 830°C to 1130°C and for a range of 1 hour to 100 hours to produce a fifth mixture. In the third step described above, an aluminum alkoxide is used as the fifth material having aluminum, and a zirconium alkoxide is used as the sixth material having zirconium. A method for producing a positive electrode active material, wherein in the second, fourth, and fifth steps, the first to third heating is carried out in an oxygen-containing atmosphere.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, manufacturing method of the same, and the battery

    JP2003178759A

  • Solid lithium ion secondary battery

    JP2012028231A

  • Lithium ion secondary battery

    JP2016062683A

  • Nonaqueous secondary battery

    JP2019165010A

  • Method for manufacturing positive electrode active material

    JP2019179758A